Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Assessing the nutritional reversibility of high-carbohydrate-induced muscle quality deterioration in male Pelodiscus sinensis: A two-phase dietary switch study - Xiangce Li; Da Yue; Xueying Shi; Xinxin Zhang; Yongqin Tu; Xiaolin Dong; Peiyu Zhang; Haiyan Liu (Aquaculture, 2026)

Structure-dependent regulation of nanoplastic uptake by humic substances in a freshwater protozoan - Ke-Da Zhang; Hong-Jie Zhang; Xin-Yuan Li; Wei Pan; Xin-Lei Wang; Ai-Jun Miao (Water Research, 2026)

Earthquake-induced acceleration control of monopole communication towers using a levered tuned mass damper - Da Li; Wuchuan Pu; Qishuo Zhang (Soil Dynamics and Earthquake Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Borehole geophysical studies in glaciers. Part II: Borehole in situ observatories - Pavel G. Talalay; Xiaopeng Fan; Bing Li; Nan Zhang; Da Gong; Jialin Hong; Yazhou Li (Earth-Science Reviews, 2026)

Thermally regulated interfacial alloy evolution enables stable Zn metal anodes - Yu Zhang; Yiyang Bi; Da Zhang; Lianshan Sun; Haoran Sun; Jian Li; Zhenyu Hu; Wanqiang Liu; Gang Huang (Chemical Engineering Journal, 2026)

Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

An orally administered colon-targeted mesalamine nano-prodrug for enhanced therapy and prevention of inflammatory bowel disease - Xiao-Han Tian; Da-Yuan Wang; Si-Yu Li; Shuna Cao; Feng Liu; Mingqing Zhang; Linqi Shi (Chemical Engineering Journal, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Temperature-regulated surfactant interfacial behavior influences shell formation and mechanical susceptibility of pesticide microcapsules - Xuewen Jian; Xin Liu; Quanbin Liu; Haixiu Bai; Xiangyang Li; Yunyu Tang; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Environmental cadmium disrupts placental angiogenesis and fetal growth via enhancing m6A modification in Wwp2 - Cheng-Fang Sun; Ye-Xin Luo; Xin-Xin Zhang; Rui Pan; Yu-Xi Wu; Jia-Ying Chen; Xin-Run Wang; Lan-Lan Wu; Si-Ting Liu; Wei Chang; Zhi Yuan; Da-Min Zhu; et al. (Environmental Pollution, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Water release regulating JsSWEET17 transcriptional expression to promote the female flower bud differentiation of Juglans sigillata - Wenwen Li; Da Yuan; Jinyan Chen; Chunxiang Li; Yuanqi Huang; Wen'e Zhang; Xuejun Pan (Journal of Plant Physiology, 2026)

Spatiotemporal radical engineering via non-destructive synchrotron lithography for multimodal functionalization of inert polymers - Hao Zhang; Xincheng Xie; Shengbin Cao; Fan Zhang; Lin Da; Yang Liu; Bomin Liu; Feng Tian; Caizhen Zhu; Xiuhong Li; Jian Xu (Chemical Engineering Journal, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

In-depth exploration into the multifaceted regulatory mechanisms of carotenoid metabolism in microalgae - Ming-Hua Liang; Chong-Ping Li; Wei-Ping Zhang; Da-Zhi Wang (Bioresource Technology, 2026)

Gut Microbiota from Patients with Long COVID Persisting for 2 Years Result in Alterations in Mice that Resemble Post-COVID Symptoms - Daya Zhang; Chen Chen; Yunqian Xie; Shuo Zhou; Da Li; Fan Zeng; Shimei Huang; Yanting Lv; Xianfeng Huang; Fengjiao Mao; Runyu Chen; Ying Mo; et al. (Probiotics and Antimicrobial Proteins, 2026)

Annexin A2 orchestrates CSFV entry route selection via the annexin A2/S100A10 heterotetrameric complex - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Jiaoyang Li; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; et al. (Veterinary Microbiology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

How clean is clean enough? Short-chain PFAS remain dominant in treated landfill leachate - Fei Chen; Zhi-Zhong Zhang; Hang Li; Si-Da Meng; Leo W.Y. Yeung; Sakhayana Danilova; Yi-Fan Li; Sheng-Qiang Fan; Zi-Feng Zhang (Journal of Environmental Management, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Scaling, performance, and quality: Machine-Learning evidence for how WWTP and compost processes shape microplastics - Ling Shu; Zhoujia Jiang; Yufan Fei; Yating Luo; Da Ouyang; Yuejin Zhang; Jing Li; Haibo Zhang (Environmental Research, 2026)

Basin-scale occurrence and seasonal behavior of per- and polyfluoroalkyl substances (PFAS) in a cold-region river system: The Songhua river basin, Northeast China - Si-Da Meng; Hang Li; Zhi-Zhong Zhang; Sakhayana Nikolaevna Danilova; Yi-Fan Li; Bing-Feng Liu; Zi-Feng Zhang; Yuan Liu (Environmental Pollution, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Robust carbon price forecasting across frequencies and scales: A novel hybrid-attention multivariate information-fusion framework with interpretable attributions - Haolin Yang; Siqi Xu; Liangke Liu; You Li; Da Zhang (Environmental Impact Assessment Review, 2026)

Correction: Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

VALD-3 Induces GSDME-Dependent Pyroptosis via ROS/JNK/Bax Pathway in Triple-Negative Breast Cancer Cells - Xuhui Zhao; Xuhong Pan; Weijie Ma; Shuang Liang; Dezhuan Da; Jiawei Liu; LingFang Zhang; Pengfei Song; Hongling Li (Biochemical Genetics, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Experimental investigation of pile anchors in sand under inclined cyclic loading for TLP supported floating offshore wind turbines - Jianbin Cui; Youhu Zhang; Shuzhao Li; Da Li; Ying Huang; Guodong Sun (Ocean Engineering, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Dual-functional Ti-MOF/g-C3N4 engineered PVDF membranes for photocatalytic self-cleaning and high-flux water remediation - Dongyuan Li; Xiaojun Peng; Rui Zhang; Yadong Chen; Peng Song; Wei Chen; Da Wang (Environmental Research, 2026)

Simultaneous removal of organic and inorganic arsenic: A critical evaluation of direct adsorption and hybrid catalytic oxidation-adsorption pathways - Huiping Zeng; Guoyang Ma; Xiaoying Zheng; Da Lin; Jie Zhang; Dong Li (Chemical Engineering Journal, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Biogeochemical evolution and iron speciation in the abandoned Yellow River Delta: deciphering the impact of anthropogenic engineering and introduced Spartina alterniflora - Zisheng Zhang; Hepin Wu; Qiao Li; Xiao Tang; Hongwu Zhou; Da Li (Frontiers in Marine Science, 2026)
Understanding sediment dynamics and anthropogenic impacts in the land-sea interaction zone of the Abandoned Yellow River Delta is challenged by complex material sources. This study aims to reconstruct sedimentary environment evolution and evaluate human influences on silty-mud tidal flats. Sediment cores were collected from a bare flat (GT) and a Spartina alterniflora marsh (HM) in the Yancheng coastal wetland, Jiangsu, China. A multi-proxy approach was applied, including grain size, organic carbon and nitrogen content, 210 Pb - 137 Cs dating, analysis of major elements and iron speciation analysis. Results indicate: (1) The GT core exhibits sandy silt characteristics, indicative of an intertidal environment. The HM core is dominated by clayey silt and silt, displaying a silt-sand binary structure, reflecting a typical silty tidal flat. Grain size characteristics suggest tidal flat accretion is collectively driven by reclamation, storm surges, tidal action, and sediment trapping by S. alterniflora . (2) Organic matter provenance analysis reveals marine sources dominate the GT core, while terrigenous sources dominate the HM core. Increasing trends of TOC, TN, and C/N with depth suggest S. alterniflora introduction likely promoted organic matter accumulation. (3) 210 Pb - 137 Cs dating yields deposition rates of 1.25 cm/a (GT) and 1.39 cm/a (HM). Combined with previous studies, regional average deposition rates show a declining trend with enhanced accretion, potentially linked to increased hydrodynamics from reclamation and the Jiangsu Coastal Current. (4) Major elements follow the Na > Al > K > Fe > Ca > Ti > Mg > Ba > Mn > Sr and the distribution of major elements is synergistically controlled by provenance, grain size effects, and biological processes; the variations in element-grain size correlations reveal the modulating effect of sedimentary composition on geochemical behavior. (5) Iron speciation content follows the order Fe ox > Fe mag > Fe carb > Fe py and increases with depth, primarily sourced from terrigenous inputs influenced by chemical weathering and marine dynamics. The sedimentary environment is oxic/suboxic, promoting TOC mineralization and hindering preservation. The Fe HR /Fe T ratio characteristics resemble those of shelf-margin marine sediments and Yellow River particulates. However, influenced by weathering, runoff, and sea-level changes, this ratio is unreliable for accurately indicating redox conditions.

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

Geniposide ameliorates DSS-induced colitis via synergistically restoring intestinal barrier integrity and inhibiting the NF-κB-NLRP3-pyroptosis axis - Ximing Yang; Da Hong; Xiaoyu Ma; Yijiu Zhang; Li Liu; Shuzhen Cheng (Food Bioscience, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

High-performance polyurethane-based ionically conductive elastomers for biomimetic skin with multimodal sensing capabilities - Xinlei Xiao; Da Song; Jiaqi Guo; Gang Li; Zhaolong Wu; Xiuyu Zhang (Chemical Engineering Journal, 2026)

A core-shell fiber membrane with synergistic radiative cooling and thermal buffering for all-weather personal comfort - Xiaohong Wu; Akbar Bashir; Chak-Yin Tang; Gary Chi-Pong Tsui; Ziqi Li; Nanhao Chen; Yichi Zhang; Yan Chen; Jie Cui; Juncheng Zhuang; Chen Liu; Yuanyuan Li; et al. (Chemical Engineering Journal, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Design, fabrication and multiple failure behavior of carbon fiber composite circumferential corrugated reinforced cylindrical shells under hydrostatic pressure - Yang-Xu Chong; Jin-Shui Yang; Da-Long Ding; Fang Yang; Hai-Dong Li; Yu-Yin Wei; Er Zhang; Jia-Dong Zeng; Guo-Tao Chen (Ocean Engineering, 2026)

Seasonal fate and removal of per- and polyfluoroalkyl substances in a wastewater treatment plant with a Bacillus bio-reactor - Sakhayana Nikolaevna Danilova; Si-Da Meng; Fei Chen; Zhi-Zhong Zhang; Bing-Feng Liu; Vasiliy Egorovich Kolodeznikov; Natalia Nikolaevna Petrova; Yi-Fan Li; Zi-Feng Zhang (Journal of Water Process Engineering, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

ESKAPE pathogens contribute largely to antibiotic resistance spread via horizontal gene transfer in aquatic environments - Shunshun Li; Zeping Gao; Yanmei Da; Ying Zhang; Zunwei Huang; Guiying Yuan; Chao Wu; Tao Huang; Qingye Sun; Guowei Zhou (Journal of Contaminant Hydrology, 2026)

Novel kinked connection component (KCC) for enhanced progressive collapse performance in CFST column–steel beam joints - Long Zheng; Yu-Chen Zhang; Yan-Li Shi; Wen-Da Wang; Yin-Quan Yu (Engineering Structures, 2026)

Mechanoadaptive conductive hydrogels with dual functionalities for epidermal sEMG monitoring and diabetic wound healing - Guoqiang Ren; Jingyun Ma; Qiuyue Peng; Pengfei Liu; Xiaobo Wang; Da Li; Yuesheng Zhang; Chaonan He; Chen Huang; Honghua Ye; Yavuz Nuri Ertas; Qingbo Xu; et al. (Chemical Engineering Journal, 2026)

A multifunctional hydrogel for inhibiting metastasis and recurrence of hepatocellular carcinoma via inflammation alleviation, metabolism regulation, and immune activation - Li-Nan Tian; Zi-Xi Wang; Youwei Zhang; Yang Liu; Huan Huang; Si-Yuan Wang; Li Wang; Wenyu Peng; Fei-Da Wu; Wei-Zhong Zhou; Hai-Feng Zhou (Chemical Engineering Journal, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Multi-objective decision model for wastewater treatment technology selection based on machine learning - Yanbo Liu; Zhaohan Zhang; Xinyi Chen; Guohong Liu; Da Li; Jiannan Li; Yanfang Song; Jinhao Duan; Kuokai Sun; Yujie Feng (Bioresource Technology, 2026)

Mitophagy protects renal tubular epithelial cells from intermittent hypoxia-induced injury via the HIF-1α/BNIP3 pathway - Xiao-Bin Zhang; Qi-Feng Gan; Yu-Xin Guo; Li-Da Chen; Li-Qin Zhang; Ling Cai; Ya-Ting Yuan; Jing-Huang Cai; Xiang-Xin Chen (Sleep and Biological Rhythms, 2026)

Whole-genome Resequencing Reveals the Sex Determination System and Develops a Sex-specific Marker in Fat Greenling (Hexagrammos otakii) - Duan Liao; Yangqing Zhang; Chunlong Miao; Shuo Li; Weijing Li; Chen Li; Ivana Felipe da Rosa; Lucas Benites Doretto; Yuyan Liu; Qian Wang; Kaiqiang Liu; Hong-Yan Wang; et al. (Marine Biotechnology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Survey of volatile organic compounds released at different temperatures from tea by direct analysis in real time mass spectrometry - Xin Geng; Zhichen Qiu; Chunyu Zhang; Hongli Li; David Da Yong Chen (Food Chemistry, 2026)

A mid‐Proterozoic coupled Sr and Li isotope excursion and its potential connection to enhanced weathering and ocean oxygenation at 1.57 Ga - Xi Chen; Ying Zhou; Simon W. Poulton; Fred T. Bowyer; Colin Mettam; Shihong Zhang; Maoyan Zhu; Da Li; Philip A.E. Pogge von Strandmann; Benjamin J.W. Mills; Graham A. Shields (Earth and Planetary Science Letters, 2026)

Metagenomic insights into species shifts and adaptation mechanisms of anammox communities treating incineration leachate - Da Kang; Yikai Zhao; Xinran Zhang; Xianyong Zeng; Xindi Fu; Bingxin Li; Zheng Ge; Liang Zhang; James P. Shapleigh; Yongzhen Peng (Chemical Engineering Journal, 2026)

Integrative bioinformatics and machine learning to explore the mechanism of Scutellaria baicalensis Georgi in TGF-β1-induced ASMCs proliferation during asthma airway remodeling - Yue Ren; Minxuan Wu; Sihan Yu; Da Li; Linghe Zhang; Yiwen Wang; Jiayi Wang; Kaiyang Liu; Wen Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A novel endophytic Kineococcus from rice against Fusarium culmorum and Fusarium sporotrichioides and whole-genome analysis - Yayun Liu; Lin Liu; Zhuanxia Lei; Ruping Zhang; Lin Zhao; Fenglan Li; Da Zhang; Qingyue Yu (Antonie van Leeuwenhoek, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Evaluation of residual virulence and protective efficacy for Brucella melitensis vaccine strain M5-90 in mice and guinea pigs - Chenchen Lu; Chenglan Zhang; Yanan Li; Zujian Qiao; Xijun Wang; Weiye Chen; Xiaoyi Chen; Qian Jiang; Da Xu; Zhigao Bu; Sen Hu (Veterinary Microbiology, 2026)

ANXA2 stabilizes mTOR at the plasma membrane to facilitate autophagic flux for CSFV release - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; Yuanji Zhang; et al. (Veterinary Microbiology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Experimental and analytical investigation on continuous two-span RC beams flexural strengthened with aluminum alloy bars - Xu Chen; Guohua Xing; Yakun Li; Jun Zhang; Da Luo; Zhaoqun Chang; Boquan Liu; Haonan Wang (Engineering Structures, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Borehole geophysical studies in glaciers. Part I: Borehole logging - Pavel G. Talalay; Nan Zhang; Xiaopeng Fan; Yazhou Li; Da Gong; Bing Li (Earth-Science Reviews, 2026)

Li3N/Li2O-rich artificial SEI formed by in-situ dielectric barrier discharge plasma for lithium metal batteries - Peng Dong; Zhipeng Xie; Fupeng Li; Shengping Hou; Da Zhang; Weiyu Gao; Yong Lei; Bin Yang; Feng Liang (Chemical Engineering Journal, 2026)

FCMI analysis of multiphysics coupling of fuel rods at the end of cycle of Xi’an pulsed reactor - Zhaohao Wang; Jinkai Zhang; Tianliang Hu; Di Yun; Duoyu Jiang; Da Li; Lixin Chen; Wenbo Liu (Annals of Nuclear Energy, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Adaptive Surface-Borehole Seismic Profile Matching and Tying Using BiGRU: A Case Study of Ultra-Deep Zero-Offset VSP in the Tarim Basin - Teng-yu Wang; Da-jun Li; Zhen Zhang; Duo-ming Zheng; Bing Fang; Pei Liu; Jing-jing Zong (Applied Geophysics, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Multi-objective optimization study of wave elimination and electricity generation performance of Savonius hydrokinetic turbine array based on metamodel - Ruiyin Song; Haihan Yu; Congjie Ren; Xi Cui; Fengshen Li; Lei Zhang; Gao Bai; Kai Chen; Da Liu (Ocean Engineering, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

The soil plastisphere: A hotspot for arsenic methylation regulated by microplastic polymer types - Kaimei Zhang; Wei Feng; Qingnan Huang; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Xianjin Tang; Haibo Zhang; Ting Guo (Environmental Research, 2026)

Enhancing capacitive energy storage in Na0.5Bi0.5TiO3-based relaxor ferroelectric ceramics by tuning polymorphic polar nanoregions - Binglong Zheng; Ying Lin; Fei Yan; Qibin Yuan; Yongzhen Ma; Yanlong Ma; Yu Zhang; Da Li; Haibo Yang (Chemical Engineering Journal, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Regulated cell death in endometrial diseases: from molecular mechanisms to targeted therapies - Duo Zi; Jing Sun; Na Zuo; Tingting Li; Junzhi Liang; Jia Hu; Zhijing Na; Hao Zhang; Lixia He; Da Li (Archives of Toxicology, 2026)

A new polyketide from Penicillium sp. HK-G2 and its inhibitory activity against α-glucosidase - Jie Zhen Shi; Yan-Li Zhang; Jin Hua Yu; Da-Mei Wang; Dong Gan; Zhong-Tao Ding (Natural Product Research, 2025)

Hexafluoropropylene oxide homologues, the novel alternatives to PFOA, induce mitochondrial dysfunction and cytotoxicity in Leydig cells through disrupting SIRT1/PGC-1α signaling pathway - Mei-Ling Le; Jia-Yu Xue; Li-Hai Wu; Xin-Yuan Zhao; Jing Ding; Yang-Yang Yuan; Yi-Qi Wan; Da-Lei Zhang (Toxicology, 2025)

A self-learning classification-based multi-objective evolutionary algorithm for machine multi-state energy-efficient flexible job shop scheduling under time-of-use pricing - Da Wang; Lina Qian; Kai Zhang; Dengwang Li; Shicun Zhao; Junqing Li (Swarm and Evolutionary Computation, 2025)

Additive effects of Lp(a) and inflammation on cardiovascular risk beyond LDL-C lowering: circulating and genetic evidence from 401,548 adults - Rui Li; Wenyue Dong; Wenxiu Wang; Youling Duan; Miao Zhang; Tao Huang; Xinwei Hua; Yi-Da Tang (Science Bulletin, 2025)

Cigarette butts: A hidden toxic time bomb for aquatic metabolism and behavior - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Environmental Pollution, 2025)

Dynamic 3-hydroxyflavone-modified D-alanine nanoparticles for metabolic-incorporation in anaerobic, pathogenic biofilms generating CO in infected periodontal pockets - Da-Yuan Wang; Jing Li; Xiao-Han Tian; Siyu Zhang; Yao Chen; Feihe Ma; Henk.J. Busscher; Jing Shen; Linqi Shi (Chemical Engineering Journal, 2025)

Vacuum freeze drying driven by photovoltaic power generation used as a green pretreatment methodology to enhance enzymatic conversion of rice straw for poly(3-hydroxybutyrate) production by Cupriavidus necator - Youwei Zhang; Wen-Chang Chang; Da-Wei Huang; Heng Chi; Zhongxuan Gou; Tingting Li (Bioresource Technology Reports, 2025)

Research and application of CMA numerical weather prediction in meteorological support for the Beijing Winter Olympics (2022) - Guo Deng; Xueshun Shen; Huiling Yuan; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Mingxuan Chen; Jianjie Wang; et al. (Science China Earth Sciences, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Analysis of the Volatile Aroma Components in ‘Yuguan’ Apple Fruit by Gas Chromatography–Mass Spectrometry - Xin Liu; Da Zhang; Jie Li; Dongmei Chen; Chaohong Zhang; Guodong Zhao; Linguang Jia; Han Wang; Xumin Wang; Tongsheng Zhao; Xinsheng Zhang (Applied Fruit Science, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

A generic compensation method for dynamic systematic errors in the geolocation of linear pushbroom satellite imagery - Da Li; Yonghua Jiang; Jingyin Wang; Shaodong Wei; Guo Zhang; Huilong Wang (Planetary and Space Science, 2025)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

Interactive effects of soil characteristics and polymer types reveal patterns of denitrifying bacteria enrichment in the soil plastisphere - Ting Guo; Shunyin Huang; Xiangyi Jin; Mengyao Xing; Williamson Gustave; Yimin Cai; Da Ouyang; Mei Li; Yanjiang Cai; Haibo Zhang (Journal of Hazardous Materials, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Ru8@NU-1000 as difunctional photocatalysts for visible-light-driven efficient CO2 reduction integrated with furfurylamine oxidation - Jiayi Zhang; Yanan Qu; Kang Bu; Jingting Lu; Da Chen; Huafeng Li; Liqun Bai (Fuel, 2025)

Polyimide porous thermoelectric fibers based on sheath core structure: A new self-powered material for early fire warning and flame retardant protection - Xinbin Ji; Yulong Xiang; Jing Guo; Fucheng Guan; Da Bao; Qiang Yang; Zheng Li; Yihang Zhang; Xin Zhang; Jiahao He (Chemical Engineering Journal, 2025)

Novel Pantoea brenneri CYD50–1 enables nitrogen-synergized enzymatic depolymerization of low-density polyethylene - Xiuya Xu; Shuai Liu; Jingli Pang; Yufan Fei; Mengyao Xing; Xiangyi Jin; Da Ouyang; Jing Li; Yating Luo; Haibo Zhang (Chemical Engineering Journal, 2025)

Siloxene coupled graphene anode membrane with Zn-ion intercalation for all-solid-state Zn-ion hybrid supercapacitors - Erhui Zhang; Da Xie; Yuchen Hong; Zhenzhen Hui; Yongsheng Zhou; Shengbiao Zheng; Jiahao Guo; Zirong Li; Jie Chen; Jing Tang (Chemical Engineering Journal, 2025)

Automatic quantification, grading and five-year prediction of myopic fundus tessellation: a multi-center, longitudinal deep learning study - Wen-Da Zhou; Li Dong; Wen-Xue Li; Li-Jian Fang; Tong Ma; Lie Ju; Zhao-Hui Wang; Yuan Luo; Wanli Miles Zhang; Xian-Gang Chang; Zong-Yuan Ge; Jost. B. Jonas; et al. (Science China Life Sciences, 2025)

ULK1-dependent phosphorylation of OGT instructs the tumorigenicity of O-GlcNAcylation - Zhuan Lv; Qingen Da; Yumiao Li; Aiyun Yuan; Guangcan Shao; Xiaoxuan Lu; Yue Wang; Xuefang Zhang; Jingjing Liu; Meng-Qiu Dong; Yuanyuan Ruan; Chen Wu; et al. (Science China Life Sciences, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

Hierarchical Replay of Multi-regional Sequential Spiking Associated with Working Memory - Ermeng Huang; Da Xu; Huangao Zhu; Zhaoqin Chen; Yulei Chen; Shujun Lei; Jiawei Liu; Chengyu T. Li; Xiaoxing Zhang (Neuroscience Bulletin, 2025)
How do millisecond-scale neural activities mediate second-scale behaviors? We recorded brain-wide activity in mice performing an olfactory working-memory task to decipher the cross-region organization of activity. Spike-correlograms analysis revealed millisecond within- and cross-region spike couplings, which were enriched among memory-encoding neurons with similar odor preferences. Spike coupling linked neurons into motifs of chains, single loops, and nested loops, especially among hippocampal and prefrontal-cortex neurons. Spike-coupling direction and activity-chain propagation aligned with that of memory-associated activity waves. Intriguingly, activity motifs were replayed before and after task performance, and during inter-trial intervals. Motifs exhibited hierarchical organization, with progressively longer time constants and the number of participating neurons. Thus, hierarchically organized and replayed cross-region spiking motifs are modulated on demand during the delay period, providing a potential mechanism for perceptual working-memory maintenance.

Soundscape diversity in urban green spaces: Spatial-temporal variations, influencing factors and optimization strategies - Yi Xiang; Qi Meng; Mengmeng Li; Da Yang; Weichen Zhang (Urban Forestry & Urban Greening, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Study of the transverse distribution of suspended sediment concentration in compound channel with emergent vegetation on floodplain - Da Li; Zhonghua Yang; Song Zhang; Man Guo (Journal of Hydrology, 2025)

Metabolic saboteurs: Tire wear particles hijack energy economy of zooplankton - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Journal of Hazardous Materials, 2025)

Remediation of chlorotetracycline contaminated water and soil by copper-coordination polymers: Effects and mechanisms - Wen-Long Duan; Wan-Ting Zhang; Tian-Da Gao; Ye-Xia Li; Lei Zhang; Li-Li Zhang; Jian Luan (Journal of Environmental Chemical Engineering, 2025)

Humic substances initiated superior photochemical pollutant conversion in environmentally relevant matrices: When ZnO met MoS2 as electron mediator - Jia-Sheng Li; Song Hu; Ling-Feng Wang; Wei Da; Ai-Yong Zhang; Lu Zhao; Jing-Yu Zhang (Journal of Environmental Chemical Engineering, 2025)

Smart construction of 8N-CuO for efficient peroxymonosulfate (PMS) activation: The synergistic effect of 8N-CuO-induced non-radical/radical pathways - Linglong Shi; Da Li; Shuangzhen Guo; Lihong Zhang; Jiaxin Bai; Mengqi Li; Sizhe Peng; Meiqi He; Yan Li; Yu Liu (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Machine learning and causal inference for disentangling air pollution reduction during the Asian Games in megacity Hangzhou - Fan Zhang; Renchang Yan; Xianman Ye; Luolan Fei; Yaofu Zhu; Xiyao Chen; Shupeng Zhu; Bing Qi; Da Xu; Weijun Li (Environmental Pollution, 2025)

BiOI/ZIF-8 Z-scheme heterojunction enhance TCH degradation under anoxic environment - Kang Bu; Yanan Qu; Jiayi Zhang; Tingya Zhang; Leyu Wu; Da Chen; Shiliang Heng; Huafeng Li; Liqun Bai (Chemical Engineering Journal, 2025)

Synergistic self-assembly of anions and cations to construct colloidal MOFs-derived binder-free electrodes for superiorcapability - Jianlong Huang; Xi Wang; Kai Wang; Quan Zhang; Shuwan Zong; Wenhao Fa; Da Li; Aitang Zhang (Chemical Engineering Journal, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Characterizing Gut Microbiota Composition and Its Correlation with Growth Variation in Sea Cucumber Apostichopus japonicus - Xinyue Tang; Ziming Li; Xinghai Liu; Yulong Wu; Kaiqi Gong; Ying Guo; Wenbing Zhang; Shuyan Chi; Shilin Liu; Da Huo; Yujia Yang (Marine Biotechnology, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Synthesis of magnetic zeolite from iron sludge and fly ash for simultaneous nitrogen and phosphorus removal - Huiping Zeng; Simin Li; Jiongru Liang; Zhanguo Li; Da Lin; Jie Zhang; Dong Li (Journal of Water Process Engineering, 2025)

Decolorization and power generation in a microbial fuel cell with pomelo peel-derived bioanode - Mingshuo Feng; Haiman Wang; Da Li; Yeting Zhang (Journal of Water Process Engineering, 2025)

Unveiling non-radical oxidation pathways in peroxymonosulfate/cobalt(II) systems: Critical role of cobalt(III) and cobalt(IV) explored by manganese(II) probing - Luwei Li; Xuecong Qian; Shilong Wang; Yun Liu; Da Wang; Huixin Zhang; Yechen An; Haijun Cheng; Jun Ma (Journal of Hazardous Materials, 2025)

Multi-omics insights into 6PPD- and 6PPDQ-induced gut-liver axis disruption and non-alcoholic fatty liver disease progression in zebrafish (Danio rerio) - Yu Feng; Hongyi Xian; Ruobing Bai; Zhiming Li; Hao Li; Long Zhang; Xiyun Huang; Yuji Huang; Boxuan Liang; Yanhong Deng; Xiaohong Yang; Xiaoqing Chen; et al. (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Dielectric barrier discharge plasma-assisted silicon oxide interface engineering for long-cycling stability of sodium-ion batteries at high rates - Yue Wu; Da Zhang; Peng Dong; Fupeng Li; Yingjie Zhou; Xu Wang; Huangkai Zhou; Feng Liang (Chemical Engineering Journal, 2025)

A Co(III)-dipyrazolate framework for atmospheric CO2 photoreduction - Yingjie Wang; Xiang-Jing Kong; Guang-Rui Si; Tao He; Da-Yu Chen; Jian-Yu Zhang; Na Xing; A-Wu Zhou; Jian-Rong Li (Chemical Engineering Journal, 2025)

Pluripotent stem cell-derived cardiomyocyte transplantation: marching from bench to bedside - Yi Hong; Jiarui Liu; Weixuan Wang; Hao Li; Weijing Kong; Xiaoxia Li; Wei Zhang; Sara Pahlavan; Yi-da Tang; Xi Wang; Kai Wang (Science China Life Sciences, 2025)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Deciphering the UAV-LiDAR contribution to vegetation classification using interpretable machine learning - Tao Huang; Lei Jiao; Yingfei Bai; Jianwu Yan; Xiping Yang; Jiayu Liu; Wei Liang; Da Luo; Liwei Zhang; Hao Wang; Zhaolin Li; Zongshan Li; et al. (Computers and Electronics in Agriculture, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Controlling high-concentration precursor crystallization to minimize photon loss in bifacial perovskite solar cells - Shan Gan; Haoxuan Sun; Min Wang; Da Dou; Siyang Zhang; Chen Li; Liang Li (Science Bulletin, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Recent advances of heteroatom-doped carbon-based materials: Synthesis, properties, environmental application, and catalytic mechanism in advanced oxidation processes - Yinliang Da; Xi Li; Yanghaofan Wang; Guotuan Xie; Siqi Liu; Luyao Zhang; Hong Liang; Yongtao Li; Bing Wang (Journal of Water Process Engineering, 2025)

Simulating the effects on carbon sinks caused by urban expansion using a coupled urban–ecological model - Yida Wang; Da Zhang; Chunyang He; Tao Qi; Penghui Li (Journal of Cleaner Production, 2025)

Rare earth ions-reinforced polycationic gel polymer electrolytes for enhancing ionic conductivity and zinc anode interface stability in flexible zinc-air batteries - Hang Zhang; Jianrong Liang; Ziran You; Ying Gao; Yachu Song; Junjie Ge; Yanhao Duan; Xingchen Yan; Da Lei; Chuanling Si; Zhengzheng Li (Chemical Engineering Journal, 2025)

The Effect of Triethanolamine Dodecylbenzene Sulfonate on Metastable Corrosion of 304 Stainless Steel - Yingdi Liao; Huan Zhang; Xin Wang; Li Chen; Chenggeng Huang; Yazhou Zhao; Bo Da (Journal of Ocean University of China, 2025)

Evolution and innovation of the metazoan burrowing behaviour from Ediacaran-Cambrian transition, eastern Yunnan - Da Li; Man Li; Yongan Qi; Guochun Zhao; Jian Fu; Fuqiang Guo; Chengjun Zhang; Jianyu Guan; Shishan Zhang (Precambrian Research, 2025)

Extracellular polymeric substance-intercalated MXene membrane for osmotic power generation - Da-Qi Cao; Kai Tang; Guri Yihuo; Yan Jin; Yi-Xuan Song; Yun-Feng Wu; Wen-Yu Zhang; Zhongguo Zhang; Ming-Guo Ma; Li Song; Xiao-Di Hao (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Discrepant effects of microplastics on soil phosphorus availability under different phosphorus fertilizer applications - Ting Guo; Chunli Zhu; Yimin Cai; Williamson Gustave; Da Ouyang; Mei Li; Haibo Zhang (Journal of Environmental Management, 2025)

Laboratory investigation of sandstone joints and strata on TBM performance using a tunnelling test platform - Wei-Qiang Xie; Xiao-Li Liu; Shao-Hui Tang; Qi Zhang; Da-Rui Ren; Qing Ma (Engineering Geology, 2025)

Characteristics of secondary microseisms generated in the Bohai Sea and their impact on seismic noise - Kang-Da Yin; Xiao-Gang Zhang; Xiao-Jun Li; Guo-Liang Mao; Xing-Xing Zhang; Xiao-Hui Jia (Applied Geophysics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Fabrication and mechanism of microspheres with tunable and control-released hydrophobicity in a wide-range: Ultra-low-density proppant - Zhenyong Li; Yang Zhou; Da Zhang; Min Xu; Rui Li; Xianyan Ren (Fuel, 2025)

Hollow-whisker modified calcium phosphate loaded with deferoxamine to promote osteoporotic bone regeneration by acting HIF-1α signaling pathway - Linyun Tan; Wacili Da; Cong Feng; Yitian Wang; Xin Hu; Guifeng Du; Hao Wang; Minghao Sun; Yuanrui Luo; Jingyang Li; Xiangfeng Li; Li Min; et al. (Chemical Engineering Journal, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

Experimental Study on the Hole-Forming Process at the Borehole Bottom During Hot Water Drilling in Ice and Its Influence Mechanisms - Zhipeng Deng; Youhong Sun; Xiaopeng Fan; Pavel Talalay; Yifan Yang; Ximu Liu; Da Gong; Bing Li; Ting Wang; Wei Wu; Nan Zhang; Xianzhe Wei (Journal of Marine Science and Engineering, 2025)
Hot water drilling is a drilling method that employs high-temperature and high-pressure hot water jetting to achieve ice melting drilling. Characterized by rapid drilling speed and large hole diameter, it is widely used for drilling observation holes in polar ice sheets and ice shelves. Understanding the hole-enlargement process at the bottom of hot water-drilled holes is crucial for rationally designing the structure of hot water drills. However, due to the complexity of heat transfer processes, no suitable theoretical model currently exists to accurately predict this process. To address this, this paper establishes an experimental platform for hot water drilling and conducts 24 sets of experiments under different drilling parameters using visualization techniques. The study reveals the influence mechanisms of drilling speed, hot water flow rate, hot water temperature, downhole drill shape, and nozzle structure on the hole-forming process at the borehole bottom. Experimental results indicate that the primary hole enlargement occurs near the nozzle, achieving 69–81% of the theoretical maximum borehole diameter. The thermal melting efficiency at the borehole bottom is approximately 80%, with about 20% of the input hot water energy heating the surrounding ice. Under identical hot water parameters, jet shapes and drill shapes exhibit minimal impact on borehole geometry. But the improvement of the jet speed and hot water temperature can accelerate the hole-forming process.

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

IGF2BPs-regulated TIN2 confers the malignant biological behaviors of gastric cancer cells - Fang Li; Yadong Zhou; Zhiming Liao; Da Huang; Ziqing Zhang; Guoqun Chen (Tissue and Cell, 2025)

Dynamic stiffness of full-scale damaged polyester mooring ropes - Yushun Lian; Yongyue Xie; Jinhai Zheng; Wenxing Chen; Da Li; Shichang Chen; Jisheng Zhang; Xiang Wu; Jiaoxue Shi; Solomon C. Yim (Ocean Engineering, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

Genomics and biodegradation properties of an oleophilic bacterium isolated from shale oil sludge - Shuang Deng; Changfu Cai; Junwei Wang; Da Qin; Liyun Yu; Jiabin Wang; Shuang Dai; Jialin Fan; Chunlong Zhang; Liyang Li; Wei Song; Xilin Hou (International Biodeterioration & Biodegradation, 2025)

Buckling behavior and failure mechanism of pultruded GFRP circular hollow section profiles with bolt-ball joints - Hengming Zhang; Da Li; Ruoyu Li; Ruijie Zhu; Feng Li (Engineering Structures, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Cooling and Exhumation of the Late Cretaceous Laojunshan Granites in Southeast Yunnan Province, China: Constraints from Fission-Track Thermochronology and Tectonic Implications - Fang Li; Hao Bai; Ye Fang; Da Zhang; Ganguo Wu; Wei Xue; Chaoyang Que; Xinming Zhang; Xiaolong He; Bojie Hu (Journal of Earth Science, 2025)

Comprehensive assessment of the significance of cellular senescence-associated genes in neuroblastoma - Yahui Han; Biyun Li; Xiaokun Yu; Jianing Liu; Menghui Zhang; Wei Zhao; Da Zhang; Jiao Zhang (Genes & Genomics, 2025)

Model tests study of multi-layer geosynthetic-reinforced pile-supported embankments and evaluation of analytical design models - Da Zhang; Guangqing Yang; Ting Li; Peng Xu; Penghui Su (Transportation Geotechnics, 2025)

Functional microorganisms in hydrogen production: Mechanisms and applications - Yonghong Fan; Feiran Zhang; Kun He; Dan Yu; Haoming Chen; Da Tian; Yixiao Shi; Zhen Li; Xiaomei Wang (Bioresource Technology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Step-path failure of the rock slopes with large intersection angles between the strikes of strata and surface: a case study - Juehao Zhang; Da Huang; Zhao Li; Zizheng Guo; Yixiang Song; Huabo Xiao (Journal of Mountain Science, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Accelerated stochastic processes of plankton community assembly due to tidal restriction by seawall construction in the Yangtze River Estuary - Xingyu Chen; Ailing Yan; Shiqiang Lu; Haoran Zhang; Da Li; Xiaodong Jiang (Marine Environmental Research, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Dual carbon isotopes constrain the sources and age variations of terrestrial organic carbon in the middle Okinawa Trough since the last deglaciation - Mengna Chen; Chenglong Su; Shuang Wang; Da-Wei Li; Hailong Zhang; Li Li; Guangxue Li; Bingyuan Xu; Jishang Xu; Meixun Zhao (Global and Planetary Change, 2025)

Gelation properties and swallowing characteristics of heat-induced whey protein isolate/chia seed gum composite gels as dysphagia food - Lin Li; Yu-Qiao Wang; Lin-Da Zhang; Jia-Nan Yan; Ce Wang; Bin Lai; Hai-Tao Wu (Food Chemistry, 2025)

Synchronized carbon capture and nitrogen removal from municipal wastewater in a novel HRAS-SNPDA system: Carbon and nitrogen metabolism pathways - Da Jin; Xiaonong Zhang; Li Zhou; Xingxing Zhang; Peng Wu; Aijie Wang (Chemical Engineering Journal, 2025)

Effect of exogenous abscisic acid on the formation and release of archeospores in Pyropia yezoensis - Li Zhang; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Steady-state analysis of Xi’an Pulse Reactor based on the multi-physics coupling method - Tianliang Hu; Duoyu Jiang; Xinyi Zhang; Zhaohao Wang; Lipeng Wang; Lu Cao; Da Li; Lixin Chen (Annals of Nuclear Energy, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

ZnCur nanoparticle-enhanced multifunctional hydrogel platform: Synergistic antibacterial and immunoregulatory effects for infected diabetic wound healing - Yan-Wen Ding; Zhi-Wei Zhang; Xin-Yu Cui; Rui-Yang Hu; Yang Li; Si-Da Huang; Si-Qi Du; Jin-Wei Dao; Dai-Xu Wei (Chemical Engineering Journal, 2025)

Experimental Study of Starting Pressure Gradient in Carbonate Gas Reservoirs - Yao Zhu; Xiao-Ping Li; Li Liao; Da-Qiang Feng; Yu-Kun Mao; Jue-Qi Li; Ke-Jie Ye; Hao Zhang (Geotechnical and Geological Engineering, 2025)

Niche Partitioning and Intraspecific Variation of Thaumarchaeota in Deep Ocean Sediments - Ronghua Liu; Xinxin He; Gaoyang Ren; Da‐Wei Li; Meixun Zhao; Laura Lehtovirta‐Morley; Jonathan D. Todd; Xiao‐Hua Zhang; Jiwen Liu (Environmental Microbiology, 2025)
Deep‐sea sediments contain a large number of Thaumarchaeota that are phylogenetically distinct from their pelagic counterparts. However, their ecology and evolutionary adaptations are not well understood. Metagenomic analyses were conducted on samples from various depths of a 750‐cm sediment core collected from the Mariana Trench Challenger Deep. The abundance of Thaumarchaeota and archaeal amoA generally decreased with depth, except for an unexpected peak midway through the core. The thaumarchaeotal metagenome‐assembled genomes were classified into diverse phylogenetic clusters associated with amoA ‐NP‐γ, amoA ‐NP‐θ, and amoA ‐NP‐δ of ammonia‐oxidising Thaumarchaeota and non‐ammonia‐oxidising lineages. The most abundant group was within amoA ‐NP‐γ, which is usually found in coastal and shallow habitats, indicating potential niche expansion from marine shallow to hadal environments. This benthic group showed within‐species genomic variations compared to the previously identified Hadal water group, suggesting microdiversification of hadal Thaumarchaeota along with niche separation between benthic and pelagic environments. Evolutionary adaptations associated with the benthic‐to‐pelagic transition included reduced genome size, loss of motility/cell adhesion, altered energy metabolism, and different mechanisms for substrate acquisition and regulation (e.g., ammonium). These findings offer new insights into the evolution of hadal Thaumarchaeota and demonstrate, for the first time, intraspecies‐level genomic variation in Thaumarchaeota related to the benthic‐versus‐pelagic niche partitioning in the deep ocean.

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Numerical investigation of free surface flow impact using an accelerated three-dimensional smoothed particle hydrodynamics - Guiyong Zhang; Xi Yang; Zhifan Zhang; Da Hui; Zhe Sun; Guangqi Liang; Peng Li (Ocean Engineering, 2024)

Deep learning-assisted detection of psychoactive water pollutants using behavioral profiling of zebrafish embryos - Ya Zhu; Lan Li; Shaokui Yi; Rui Hu; Jianjun Wu; Jinqian Xu; Junguang Xu; Qinnan Zhu; Shijia Cen; Yuxuan Yuan; Da Sun; Waqas Ahmad; et al. (Journal of Hazardous Materials, 2024)

Enhanced biofouling resistance of polyvinylidene fluoride ultrafiltration membranes using crayfish shell biochar with calcium species - Dawei Zhang; Liqing Ma; Yuewu Da; Weiying Li; Meijuan Chen; Kan Hu; Xiangzhou Meng; Yao Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2024)

Relationship between MO/(SiO2+Al2O3) of materials—amorphous gel structure—properties of the one-part FA-Slag-based AAMs - Da-Wang Zhang; Tian-Tian Yang; Xiao-Guang Xu; Yi-Ren Wang; Hui Li (Journal of Environmental Chemical Engineering, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

A tartaric acid (TA)-coated iron-based biochar as heterogeneous fenton catalyst for enhanced degradation of dibutyl phthalate - Xi Li; Guotuan Xie; Xue Gu; Guisen Zhang; Yinliang Da; Yanghaofan Wang; Hong Liang; Yongtao Li; Bing Wang (Environmental Pollution, 2024)

Sample-to-answer point-of-care testing platform for quantitative detection of small molecules in blood using a smartphone-and microfluidic-based nanoplasmonic biosensor - Hongli Fan; Rui Li; Youqian Chen; Qiang Da; Chenchen Xiong; Yiyi Zhang; Zhiguo Qin; Gang L. Liu; Liping Huang (Chemical Engineering Journal, 2024)

Seasonal variations in psychophysiological stress recovery from street greenery: A virtual reality study on vegetation structures and configurations - Chenlu Da; Yongsheng Li; Xinmei Gao; Xiaoxu Zhang; Yuxi Yang; Huiying Ma; Baihe Zhao; Tianxu Hu; Yongcan Ma; Jinxuan Liu; Ling Qiu; Tian Gao (Building and Environment, 2024)

A Comparative Proteomics Study Revealing the Impact of Growing Region and Cultivar on Protein Expression in the Leaves of Nicotiana tabacum Plants - Yongxu Hu; Min Chen; Gang Li; Da Wu; Xiangmin Zhang (Plant Molecular Biology Reporter, 2024)

Association Between Neuroinflammation and Parkinson’s Disease: A Comprehensive Mendelian Randomization Study - YiNi Wang; XinYu Shi; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Bai-Xiang Li; Kun Ma (Molecular Neurobiology, 2024)

Shoot Organogenesis from Tetrastigma hemsleyanum Leaf and Petiole Explants, and Subsequent Plant Regeneration and Acclimatization - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Jianrong Li; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (Journal of Plant Growth Regulation, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Centrifugated lateral flow assay strips based on dual-emission carbon dots modified with europium ions for ratiometric determination and on-site discrimination of tetracyclines in environment - Houwen Hu; Haoming Xing; Yihao Zhang; Xinru Liu; Sineng Gao; Linfan Wang; Tingting Li; Ting Zhang; Da Chen (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

The effect of lambda-cyhalothrin nanocapsules on the gut microbial communities and immune response of the bee elucidates the potential environmental impact of emerging nanopesticides - Dezheng Guo; Zhongyu Li; Yiwen Zhang; Wei Zhang; Chen Wang; Da-xia Zhang; Feng Liu; Zheng Gao; Baohua Xu; Ningxin Wang (Journal of Hazardous Materials, 2024)

Mechanisms of inhibition and recovery under multi-antibiotic stress in anammox: A critical review - Xu Ji; Xiaonong Zhang; Ting Ju; Li Zhou; Da Jin; Peng Wu (Journal of Environmental Management, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Functionalized porphyrin as a carrier bridge and a passivator for perovskite solar cells - Longchen Tao; Haitao Zhang; Xinyu Zhu; Chenhan Qi; Tianhong Ye; Niping Chen; Lixin Xiao; Baojun Li; Xufei Sun; Da-Qin Yun; Lingling Zheng (Chemical Engineering Journal, 2024)

Robust PD/A biofilms sustain advanced real municipal wastewater treatment: Reinforcement of interspecific communication and electron transfer - Xiaonong Zhang; Naif Abdullah Al-Dhabi; Zixuan Zhu; Xingxing Zhang; Li Zhou; Da Jin; Wangwang Tang; Duanliang Hong; Nkonogumo Paul Luchanganya; Hongbo Guo; Peng Wu; Aijie Wang (Chemical Engineering Journal, 2024)

Optimization of Connection Parameters of Self-Adaptive Modular Floating Wind Farms - Yuming Zhang; Da Li; Haixiao Liu (Journal of Marine Science and Engineering, 2024)
Connection parameters are the key factors influencing the responses of modular floating structures; due to the complexity of structural response properties, the assessment and optimization of connection parameters are still vital issues in designing modular floating structures. In the present work, for a novel structural configuration of self-adaptive modular floating wind farms based on existing works from the case of a mobile offshore base, a quantified approach for the assessment of connection parameters is established based on frequency domain numerical analysis taking into account both the economic effects and generalized performance. Based on the quantified assessment, an optimization process is carried out, to obtain a connection parameter combination. From the optimized connection parameters, it can be found that the most appropriate tri-axial stiffness according to present studies is in the magnitude from 1 × 106 to 7 × 107 N/m, and the damping ratio is close to 1.0 for most connection structures. By contrast with feasible uniform connection parameters, the optimization methodology is confirmed to be able to reduce both connection parameters and responses. Then, a time domain approach for the calculation of motions of interconnected modular floating structures taking into account geometry nonlinearity is proposed and obtained in good accordance with the frequency domain results, and the effectiveness of both the frequency domain and time domain is validated.

Thyroxine regulates pig Sertoli cell line proliferation and maturation through the IKK/NFκB and p38 MAPK signaling pathways - Jing Li; Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Chun-Yan Bai; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sea surface carbon dioxide during early summer at the Tuandao nearshore time series site - Lu Cao; Yongqi Qiu; Liang Xue; Yingying Zhang; Shuwei Zhang; Ning Wu; Da Yuan; Quanlong Li; Zheng Zhao; Ning Wang; Yan Zhou; Wei Yang; et al. (Marine Environmental Research, 2024)

Gut antibiotic resistome during pregnancy associates with the risk of gestational diabetes mellitus: New evidence from a prospective nested case−control study - Jing Li; Zhonghan Sun; Fengjiang Sun; Yuwei Lai; Xinzhu Yi; Zhang Wang; Jiaying Yuan; Yayi Hu; An Pan; Xiong-Fei Pan; Yan Zheng; Da Chen (Journal of Hazardous Materials, 2024)

Vapor-phase reduction synthesis of N, S co-doped graphene/MWCNT hybrid membrane for all-solid-state supercapacitors and adsorption of organic pollutants - Erhui Zhang; Yutong Zheng; Da Xie; Yongsheng Zhou; Shengbiao Zheng; Zirong Li; Jing Tang; Jiahao Guo (Journal of Environmental Chemical Engineering, 2024)

Impact of plant and animal proteins with transglutaminase on the gelation properties of clam Meretrix meretrix surimi - Lin-Da Zhang; Lin Li; Qian Zhang; Yu-Qiao Wang; Yue Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Bioscience, 2024)

Epoxy resin gel particles with adjustable stickiness and deformability for pesticide delivery - Jiang Du; Da-Xia Zhang; Li-Jian Hao; Kun Zhuang; Feng Liu; Chao-Bin Xue (Chemical Engineering Journal, 2024)

Low-dose 60Co-γ-ray irradiation promotes the growth of cucumber seedlings by inducing CsSAUR37 expression - Shengnan Li; Ke Lu; La Zhang; Lianxue Fan; Wei lv; Da jun Liu; Guojun Feng (Plant Molecular Biology, 2024)

Effect of fracture structure on heat transfer in heat pipes in a submarine hydrothermal reservoir - Gaowei Yi; Yan Li; Da Zhang; Shiqiao Zhou (Computational Geosciences, 2024)

Characteristics, Distribution Patterns, and Classification of Volcanic Reservoirs in the Huanghua Depression, Bohai Bay Basin, China - Jian Huang; Changqian Ma; Shihui Zhang; Muyue Xu; Da Lou; Chongbiao Leng; Mutian Qin; Hongjun Li (Journal of Earth Science, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

Research on pollution identification and safety thresholds based on the olfactory effect on a halogenated hydrocarbon contaminated site - Xuwei Li; Wenyi Xie; Ya Zhang; Yun Chen; Mei Li; Lingya Kong; Da Ding; Shaopo Deng (Chemosphere, 2024)

Performance research and improvement of ultra-high-speed R290 rotary compressor - Hua Zhong; Bowen Lei; Li Zhang; La Da; Che Wang; Jianhua Wu (International Journal of Refrigeration, 2024)

Understanding the structural relation and electrochemical evolution between ZnGeP2 and ZnSiP2 twin phosphides for advanced Li-ion batteries - Wei Liang; Bin Chen; Da Li; Xuhao Liu; De Li; Xuan Tian; Panpan Zhang; Xing Lu; Yaqing Wei; Yong Chen (Chemical Engineering Journal, 2024)

Continuous deposition of pre-aged organic carbon in the southern Mariana Trench since the last deglaciation - Da-Wei Li; Mengna Chen; Shuai Liu; Hailong Zhang; Zicheng Wang; Xiaoyan Ning; Jiwei Tian; Meixun Zhao (Chemical Geology, 2024)

Genome-wide analysis of long non-coding RNAs involved in the fruit development process of Cucumis melo Baogua - Ya-hui Li; Chun Liu; Run-zhe Xu; Yu-peng Fan; Ji-yuan Wang; Hu Li; Jian Zhang; Hui-jun Zhang; Jing-jing Wang; Da-kui Li (Physiology and Molecular Biology of Plants, 2024)

Analysis of the Relationship Between Parkinson’s Disease and Diabetic Retinopathy Based on Bioinformatics Methods - XinYu Shi; YiNi Wang; YaPing Yin; Fei Yang; YiNan Zhang; Xin He; Da Wen; Kun Ma; Bai-Xiang Li (Molecular Neurobiology, 2024)

Emerging applications and mechanisms of algal-bacterial symbiosis on sustainable wastewater treatment: A comprehensive review - Da Jin; Xiaonong Zhang; Li Zhou; Xingxing Zhang; Peng Wu (Journal of Water Process Engineering, 2024)

The effects of an online food waste reduction platform in university canteens in Wuhan, China - Wanqi Du; Li Xue; Da Xu; Hui Zhang; Gang Liu; Huabo Duan; Junjie Dong; Jinyi Chen; Huali Zhang (Journal of Cleaner Production, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Polyacrylonitrile In-Situ reinforced polyimide superhydrophobic porous fibers: A miraculous thermal insulation and flame-retardant material - Xinbin Ji; Yulong Xiang; Jing Guo; Fucheng Guan; Xiaoqing Xiong; Da Bao; Qiang Yang; Minghan Li; Yihang Zhang; Zheng Li; Jianbin Sun (Chemical Engineering Journal, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Shoot propagation, regeneration, and callus induction and differentiation, of Axonopus compressus (Swartz) Beauv - Yuping Xiong; Zhenpeng Wei; Junyu Liu; Jianrong Li; Shuguang Jian; Xinhua Zhang; Yuan Li; Zhan Bian; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2024)

Impact on sulfadiazine bio-accessibility in soils through organic diffusive gradients in thin films (o-DGT): Differentiation based on microplastic polymers, aging, and soil properties - Baochen Li; Chunli Zhu; Da Ouyang; Ting Guo; Xiaodong Wu; Yimin Cai; Haibo Zhang (Science of The Total Environment, 2024)

Cancer risk associated with low-dose ionizing radiation: A systematic review of epidemiological and biological evidence - Shu Min Tao; Le Le Wang; Min Da Li; Jing Wang; Hong Mei Gu; Long Jiang Zhang (Mutation Research - Reviews in Mutation Research, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Double gradient coupling heterostructure design accurately regulates the anion process of the Li-rich cathode - Chaoliang Zheng; Da Zhang; Di Zhang; Jianling Li (Chemical Engineering Journal, 2024)

Effects of abamectin nanocapsules on bees through host physiology, immune function, and gut microbiome - Dezheng Guo; Ying Wang; Zhongyu Li; Da-xia Zhang; Chen Wang; Hongfang Wang; Zhenguo Liu; Feng Liu; Xingqi Guo; Ningxin Wang; Baohua Xu; Zheng Gao (Science of The Total Environment, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

PLD2 deletion ameliorates sepsis-induced cardiomyopathy by suppressing cardiomyocyte pyroptosis via the NLRP3/caspase 1/GSDMD pathway - Jun Li; Da Teng; Wenjuan Jia; Lei Gong; Haibin Dong; Chunxiao Wang; Lihui Zhang; Bowen Xu; Wenlong Wang; Lin Zhong; Jianxun Wang; Jun Yang (Inflammation Research, 2024)
Objective Sepsis-induced cardiomyopathy (SICM) is a life-threatening complication. Phospholipase D2 (PLD2) is crucial in mediating inflammatory reactions and is associated with the prognosis of patients with sepsis. Whether PLD2 is involved in the pathophysiology of SICM remains unknown. This study aimed to investigate the effect of PLD2 knockout on SICM and to explore potential mechanisms. Methods The SICM model was established using cecal ligation and puncture in wild-type and PLD2-knockout mice and lipopolysaccharide (LPS)-induced H9C2 cardiomyocytes. Transfection with PLD2-shRNA lentivirus and a PLD2 overexpression plasmid were used to interfere with PLD2 expression in H9C2 cells. Cardiac pathological alterations, cardiac function, markers of myocardial injury, and inflammatory factors were used to evaluate the SICM model. The expression of pyroptosis-related proteins (NLRP3, cleaved caspase 1, and GSDMD-N) was assessed using western blotting, immunofluorescence, and immunohistochemistry. Results SICM mice had myocardial tissue damage, increased inflammatory response, and impaired heart function, accompanied by elevated PLD2 expression. PLD2 deletion improved cardiac histological changes, mitigated cTNI production, and enhanced the survival of the SICM mice. Compared with controls, PLD2-knockdown H9C2 exhibits a decrease in inflammatory markers and lactate dehydrogenase production, and scanning electron microscopy results suggest that pyroptosis may be involved. The overexpression of PLD2 increased the expression of NLRP3 in cardiomyocytes. In addition, PLD2 deletion decreased the expression of pyroptosis-related proteins in SICM mice and LPS-induced H9C2 cells. Conclusion PLD2 deletion is involved in SICM pathogenesis and is associated with the inhibition of the myocardial inflammatory response and pyroptosis through the NLRP3/caspase 1/GSDMD pathway.

Transient multi-physics coupling analysis of the Xi'an Pulsed Reactor under pulsed condition - Duoyu Jiang; Peng Xu; Tianliang Hu; Xinbiao Jiang; Da Li; Xiaoyan Tian; Lipeng Wang; Yongping Wang; Xinyi Zhang; Lu Cao (Annals of Nuclear Energy, 2024)

Rotavirus infection inhibits SLA-I expression on the cell surface by degrading β2 M via ERAD-proteasome pathway - Zhaoyang Jing; Ling Wu; Yudi Pan; Liaoyuan Zhang; Xin Zhang; Da Shi; Hongyan Shi; Jianfei Chen; Zhaoyang Ji; Jiyu Zhang; Tingshuai Feng; Jin Tian; et al. (Veterinary Microbiology, 2024)

Sources apportionments of heavy metal(loid)s in the farmland soils close to industrial parks: Integrated application of positive matrix factorization (PMF) and cadmium isotopic fractionation - Fanglei Shao; Kainan Li; Da Ouyang; Jiawen Zhou; Yating Luo; Haibo Zhang (Science of The Total Environment, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Corrigendum to “Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface” [Ocean Eng. 297, April 2024] - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

An active-bending sheltered pathway based on bamboo strips for indoor temporary applications: Design and construction - Junsong Wang; Da Shi; Chenyu Zhou; Qiu Zhang; Zhi Li; Francesco Marmo; Cristoforo Demartino (Engineering Structures, 2024)

Low-frequency Stimulation at the Subiculum Prevents Extensive Secondary Epileptogenesis in Temporal Lobe Epilepsy - Yujia Shen; Yiwei Gong; Xiaoli Da; Shajing Gao; Shuo Zhang; Minjuan Sun; Yuanzhi Yang; Xiaoyun Qiu; Menghan Li; Yang Zheng; Fan Fei; Yi Wang; et al. (Neuroscience Bulletin, 2024)

Scientific Advances and Weather Services of the China Meteorological Administration’s National Forecasting Systems during the Beijing 2022 Winter Olympics - Guo Deng; Xueshun Shen; Jun Du; Jiandong Gong; Hua Tong; Liantang Deng; Zhifang Xu; Jing Chen; Jian Sun; Yong Wang; Jiangkai Hu; Jianjie Wang; et al. (Advances in Atmospheric Sciences, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

Theoretical and numerical studies of the coupled Bjerknes and buoyancy effects on the dynamics of an underwater explosion bubble near a free surface - Lei Wang; Yun-Feng Zhang; Hao Li; Ya-Guang Sui; Ke Wu; Da-Min Zhang; Wen-Hao Yao (Ocean Engineering, 2024)

Determining priority control toxic metal for different protection targets based on source-oriented ecological and human health risk assessment around gold smelting area - Yan Zhou; Da Ding; Yuanchao Zhao; Qun Li; Dengdeng Jiang; Zhengyong Lv; Jing Wei; Shengtian Zhang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Environmentally responsible steel-slag-based solid particles for highly efficient and durable solar selective absorptance and thermal storage - Lili Yang; Chong Li; Yun Da; Jinrui Zhang; Gang Wang (Journal of Cleaner Production, 2024)

Heterologous expression of taxane genes confers resistance to fall armyworm in Nicotiana benthamiana - Zhenlu Xu; Yaohua Zhai; Huimin Chang; Da Yan; Pengliang Ge; Guangming Ren; Lijun Zhang; Ye Yuan; Ruoyan Wang; Wentao Li; Fuguang Li; Maozhi Ren; et al. (Plant Cell Reports, 2024)

Tropical Cyclone Monitoring and Analysis Techniques: A Review - Chuanhai Qian; Ying Li; Yinglong Xu; Xin Wang; Zenghai Zhang; Gaozhen Nie; Da Liu; Shiwen Zhang (Journal of Meteorological Research, 2024)

Polyethylene microplastic modulates lettuce root exudates and induces oxidative damage under prolonged hydroponic exposure - Yimin Cai; Yangyang Xu; Guanlin Liu; Baochen Li; Ting Guo; Da Ouyang; Mei Li; Shuai Liu; Yingyu Tan; Xiaodong Wu; Haibo Zhang (Science of The Total Environment, 2024)

Chiral separation and bioactivities of six pairs of enantiomeric dilignans from Magnolia officinalis var. biloba - Ying-Da Zang; Cai-xia Zang; Jin-Ying Tian; Kai-Ling Xu; Chuan Li; Chuang-Jun Li; Yang Yang; Fei Ye; Dan Zhang; Dong-Ming Zhang; Jie Ma (Phytochemistry, 2024)

Characteristics of dew/hoar frost from Artemisia ordosica and bare soil based on weighing lysimeters in a semi-arid region - Bin Ran; Chengcheng Gong; Yu-Li Wang; Zaiyong Zhang; Wenke Wang; Jingbo Yang; Da Xu (Journal of Hydrology, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Maize yield increased by matching canopy light and nitrogen distribution via controlled-release urea /urea adjustment - Huan Li; Yiming Zhu; Gaofeng Wang; Rongrong Liu; Da Huang; Miaomiao Song; Yihan Zhang; Hao Wang; Yongchao Wang; Ruixin Shao; Jiameng Guo; Qinghua Yang (Field Crops Research, 2024)

The genesis and resource potential of gold deposits in the Liaodong Peninsula - Rixiang Zhu; Jin-Hui Yang; Gongwen Wang; Qingdong Zeng; Guoqiang Xue; Tao Xu; Xinghui Li; Peng Zhang; Da Lei; Guang Zhu (Science China Earth Sciences, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Characterization of microbial contamination in agricultural soil: A public health perspective - Xiaodi Li; Lin Zhu; Si-Yu Zhang; Jingpeng Li; Da Lin; Meizhen Wang (Science of The Total Environment, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

Highly effective synthesis of novel structured phospholipid emulsifiers using magnetically recyclable Fe3O4@SiO2/M (M = Zn or Al) composite - Jia Ma; Jiang-Hua Zhang; Hua-Wei Zhang; Qian-Qian Du; Zi-Xuan Li; Zhi-Fei Yang; Sha-Sha Yang; Da-Yong Zhou (Food Chemistry, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Intensified nitrogen and phosphorus removal and mechanism revelation in constructed wetlands amended with iron-carbon based substrate towards low C/N ratio wastewater - Zhiyi Zhang; Da Li; Guohong Liu; Tongtong Liu; Yujie Feng (Chemical Engineering Journal, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Inhibition of nucleotide metabolism with dual-template epitope imprinted nanoparticles for targeted HER2+ tumor therapy - Xing-Hui Ren; Lei Shi; Zi-Bo Ma; Da-Wei Wang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Chemical Engineering Journal, 2024)

Layered PrZnOX (X = P, As) compounds: Promising n-type thermoelectric materials with low lattice thermal conductivity - Xiaodong Li; Shulin Bai; Da Wan; Jingyi Zhang; Mengxiu Wu; Peng Ai; Shuwei Tang (Chemical Engineering Journal, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Dung-soil microbial community coalescence can exert dual effects on alpine grasslands through changing soil microbiomes - Dong Liu; Zelin Wang; Kaifang Liu; Song Zhang; Feiling Yang; Jie Li; Feng Liu; Da Bao; Rongxiao Che (Journal of Soils and Sediments, 2024)

Construction of methylation driver gene-related prognostic signature and development of a new prognostic stratification strategy in neuroblastoma - Yahui Han; Biyun Li; Jian Cheng; Diming Zhou; Xiafei Yuan; Wei Zhao; Da Zhang; Jiao Zhang (Genes & Genomics, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

IFITM3 restricts porcine deltacoronavirus infection by targeting its Spike protein - Jianxiao Wu; Rongfeng Tang; Xiaorong Zhang; Mingzhe Gao; Longjun Guo; Liaoyuan Zhang; Da Shi; Xin Zhang; Hongyan Shi; Hongying Song; Li Feng; Jianfei Chen (Veterinary Microbiology, 2024)

Chlorogenic acid ameliorates the heat stress-induced impairment of porcine Sertoli cells by suppressing oxidative stress and apoptosis - Shao-Xuan Zhang; Da-Li Wang; Jia-Jia Qi; Yu-Wei Yang; Hao Sun; Bo-Xing Sun; Shuang Liang (Theriogenology, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Quantitative effect of adding percentages of anammox granules on the start-up process and microbial community analysis - Jialu Huang; Xiaolong Wang; Zhiqiang Qi; Mengqian Zhang; Ruiqin Kang; Chao Liu; Da Li (Journal of Environmental Management, 2024)

Bell pepper derived nitrogen-doped carbon dots as a pH-modulated fluorescence switching sensor with high sensitivity for visual sensing of 4-nitrophenol - Guoqiang Guo; Tingting Li; Ziyi Liu; Xinyu Luo; Ting Zhang; Siyuan Tang; Xu Wang; Da Chen (Food Chemistry, 2024)

Application of urea-based magnetic covalent organic framework as sorbent for the determination of coumarin and its derivatives in food samples combined with liquid chromatography-mass spectrometry - Xue-Mei Nie; Yin-Long Li; Xiu-Li Xu; Feng-Ming Chen; Feng Zhang; Da Chen (Food Chemistry, 2024)

LBM-PFM simulation of the effect of non-condensable gas on the directional crystallization of seawater - Yina Luo; Da Zhang; Han Yuan; Yan Li (Desalination, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

Application of TRMM for Spatio-Temporal Analysis of Precipitation in the Taiwan Strait and Its Adjacent Regions - Yaozhao Zhong; Da Li; Lei Wang; Caiyun Zhang; Feng Zhang (Journal of Marine Science and Engineering, 2023)
Precipitation patterns are highly valued in the fields of weather forecasting, water resource management, and estuary environment research. In this study, daily and monthly precipitation TRMM data from 1998 to 2019 were selected, and EOF analysis was employed to analyze the precipitation patterns of the Taiwan Strait and its neighboring regions. We obtained the following results: (1) The rainy season (May–June) is the main contributor to precipitation in the study area. The EOF first mode reflected the overall consistency of the precipitation spatial distribution. However, within each river basin, the magnitude of precipitation variation is spatially different. The magnitude of precipitation variation is significant in the northwestern part of the Minjiang River basin, the southwestern part of the Jiulong River basin, and the southwestern corner of the Hanjiang River basin. These areas happen to correspond to the mountain areas, revealing that topographic precipitation plays a role in the spatial distribution of precipitation in the three river basins. (2) The spatial distributions of the EOF first mode and of precipitation during El Niño in the Minjiang River basin are consistent. This reveals that ENSO is probably the dominant factor in precipitation in the Minjiang River basin. The significant increase in precipitation during El Niño compared with a normal year in the Minjiang River basin confirms this point. (3) In all three strong El Niño years, 1998, 2010, and 2016, the Minjiang River basin experienced significant heavy precipitation in the fall and winter, whereas the Jiulong River and Hanjiang River basins did not (except in 2016). In other words, the Minjiang River basin is more affected by ENSO, while the Jiulong River and Hanjiang River basins are only limitedly impacted by ENSO.

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Assessment of the seismic hazard in North China by combining micro-seismicity records and geodetic observations - Yuan Gao; Wei Qu; Qin Zhang; Jiuyuan Li; Da Li; Yuhao Wang; Ming Hao (Tectonophysics, 2023)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Exploring the antioxidant “cut-off effect” of gallic acid alkyl esters in dried oysters (Crassostrea gigas) during storage - Guan-Hua Zhao; Ying Luo; Qi Li; Min Zhang; Fa-Wen Yin; Da-Yong Zhou (Food Bioscience, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Gametophyte Development and Sporophyte Regeneration of Alsophila spinulosa - Yuping Xiong; Yujie Zeng; Junyu Liu; Xiaohong Chen; Yuan Li; Xinhua Zhang; Zhan Bian; Jaime A. Teixeira da Silva; Songjun Zeng; Kunlin Wu; Guohua Ma (Journal of Plant Growth Regulation, 2023)

Long-term influence of chloroxylenol on anaerobic microbial community: Performance, microbial interaction, and antibiotic resistance gene behaviors - Jingwei Wang; Shuang Shan; Da Li; Zhaojing Zhang; Qiao Ma (Science of The Total Environment, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Investigation and application of microscopic mechanism of multiple bubble movement on directional frozen crystallization of seawater - Da Zhang; Yan Li; Han Yuan (Desalination, 2023)

Research progress of solid electrolyte interphase for sodium metal anodes - Minjie Hou; Yingjie Zhou; Feng Liang; Huaping Zhao; Deyang Ji; Da Zhang; Liqiang Li; Yong Lei (Chemical Engineering Journal, 2023)

Piezoelectric self-power supply driven by ferroelastic host–guest supramolecule with considerable electromechanical conversion capability - Meng-Meng Lun; Jia-Qi Luo; Zhi-Xu Zhang; Jie Li; Li-Yan Xie; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2023)

Metagenomics insights into high-rate nitrogen removal from municipal wastewater by integrated nitrification, partial denitrification and Anammox at an extremely short hydraulic retention time - Junjiang Chen; Xiaonong Zhang; Li Zhou; Zixuan Zhu; Zhiqiang Wu; Kangyu Zhang; Yiwen Wang; Ting Ju; Xu Ji; Da Jin; Peng Wu; Xingxing Zhang (Bioresource Technology, 2023)

Preparation of basic magnesium carbonate nanosheets modified pumice and its adsorption of heavy metals - Yong Zhang; Yi-Fan Xiao; Guang-Song Xu; Min-Da Xu; De-Cai Wang; Zhen Jin; Jia-Qi Liu; Li-Li Yang (Environmental Science and Pollution Research, 2023)

Microplastic formation and simultaneous release of phthalic acid esters from residual mulch film in soil through mechanical abrasion - Da Ouyang; Yifan Peng; Baochen Li; Fanglei Shao; Kainan Li; Yiming Cai; Ting Guo; Haibo Zhang (Science of The Total Environment, 2023)

A multi-drive aerodynamic load simulator for floating wind turbine model tests: Development, test and application - Binrong Wen; Zehao Liang; Hang Zhang; Ke Fan; Ye Wang; Da Li; Xinliang Tian; Zhike Peng (Ocean Engineering, 2023)

Occupant behavior modules development for coupled simulation in DeST 3.0 - Xiaoyu Jia; Yiqun Pan; Mingya Zhu; Han Zhu; Zhengrong Li; Jingsi Zhang; Xiang Zhou; Song Pan; Chuang Wang; Da Yan; Zejun Wu; Huiyan Deng; et al. (Energy and Buildings, 2023)

The culprit for the declining performance of anaerobic reactors caused by calcification: Bioavailability deterioration - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

Ecological distribution of anaerobic granular sludge towards efficient anaerobic reactor - Wenda Chen; Huiming Tang; Dongdong Xu; Wenji Li; Chao Pan; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Bioresource Technology, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Description of Xanthocytophaga agilis sp. nov. and Xanthocytophaga flavus sp. nov. of the new genus Xanthocytophaga gen. nov and the proposal of Rhodocytophagaceae fam. nov. within the order Cytophagales - Xianjiao Zhang; Guang-Da Feng; Yang Liu; Fan Yang; Yanxuan Li; Xiaoqin Deng; Honghui Zhu; Qing Yao (Archives of Microbiology, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Middle to late Holocene environmental evolution and sea level change on the west coast of Bohai Bay - Siyu Wang; Yuecong Li; Baoshuo Fan; Yihang Cao; Hanfei You; Rongrong Wang; Yawen Ge; Shuoqiang Da; Zijing She; Zhen Zhang; Shengrui Zhang; Cange Li (Quaternary International, 2023)

Distinct variations and mechanisms for terrestrial OC 14C-ages in the Eastern China marginal sea sediments since the last deglaciation - Mengna Chen; Da-Wei Li; Hailong Zhang; Zicheng Wang; Meixun Zhao (Quaternary Science Reviews, 2023)

Five long-distance dispersals shaped the major intercontinental disjunctions in Tectariaceae s.l. (Polypodiales, Polypodiopsida) - Xia Wan; Liang Zhang; Samuli Lehtonen; Hanna Tuomisto; Da-Wei Zhang; Xin-Fen Gao; Li-Bing Zhang (Molecular Phylogenetics and Evolution, 2023)

Linking morphological features to anammox communities in a partial nitritation and anammox (PN/A) biofilm reactor - Da Kang; Liang Zhang; Shenhua Yang; Jialin Li; Yongzhen Peng (Journal of Environmental Management, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Towards intensified preservation technology of anammox granular sludge: Insights into the role of energy support - Chao Pan; Wenji Li; Dongdong Xu; Wenda Chen; Leiyan Guo; Da Kang; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Characterization of sandalwood (E,E)-α-farnesene synthase whose overexpression enhances cold tolerance through jasmonic acid biosynthesis and signaling in Arabidopsis - Xinhua Zhang; Xiaohong Chen; Jaime A. Teixeira da Silva; Ting Zhang; Yuping Xiong; Yuan Li; Yunfei Yuan; Xiaoping Pan; Guohua Ma (Planta, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

RNA-seq analysis reveals an immunomodulatory peptide from highland barley activating RAW264.7 macrophages via TNF/NF-κB signaling pathway - Yan Liu; Xin Chen; Jia-Yi Yang; Zhi Jian Guo; Qin Wu; Li-Da Zhang; Xuan-Wei Zhou (Functional & Integrative Genomics, 2023)

Crosstalk Between the Mitochondrial Dynamics and Oxidative Stress in Zinc-induced Cytotoxicity - Qingwen Yang; Junjie Yang; Xuesong Liu; Yi Zhang; Yue Li; Da Ao; Peng Zhong; Kang Yong (Biological Trace Element Research, 2023)

Seismogenic structure of the 2020 Jiashi, Xinjiang Ms 5.4 and Ms 6.4 moderate earthquakes - Shan-Shan Liang; Guang-Wei Zhang; Xiao-Ning Huang; Li-Ye Zou; Yan-Qiong Liu; Yun-Da Ji (Applied Geophysics, 2023)

Effect of copper ions on transformation of organic sulfur in cationic exchange resins in Li2CO3–Na2CO3–K2CO3 molten-salt system - Zhi Zhang; Yun Xue; Yue-Lin Wang; Wen-Da Xu; Yong-De Yan; Yang-Hai Zheng; Fu-Qiu Ma; Guo-Qiang Li (Chemosphere, 2023)

Occurrence and screening- flotation separation for the beneficiation of rare earth elements and yttrium (REY) in core sediments from the Pacific Ocean - Anni Ouyang; Wenliang Xiong; Xiaoyu Li; Da Chen; Lijun Zhang; Peng Jiang (Marine Geology, 2023)

Industrial symbiosis promoting material exchanges in Ulan Buh Demonstration Eco-industrial Park: A multi-objective MILP model - Hao Yu; Lin Da; Yalun Li; Yanqiong Chen; Qingdan Geng; Zhibin Jia; Yun Zhang; Jinhua Li; Caixia Gao (Journal of Cleaner Production, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

UV cross-linked injectable non-swelling dihydrocaffeic acid grafted chitosan hydrogel for promoting wound healing - Jianqun Wang; Wenxia Xu; Wenxuan Zhang; Junlong Da; Lixue Liu; Xiaowei Huang; Chubo Yang; Yuanbo Zhan; Han Jin; Ying Li; Bin Zhang (Carbohydrate Polymers, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Discovery of a substance that enhances the immune response in Litopenaeus vannamei against WSSV: Baicalein, a major component of Scutellaria baicalensis - Li-Peng Shan; Ling Hu; Xu Zhang; Da-Wei Song; Yang Hu; Lei Liu; Jiong Chen (Aquaculture, 2023)

Polyethylene and polyvinyl chloride microplastics promote soil nitrification and alter the composition of key nitrogen functional bacterial groups - Shunyin Huang; Ting Guo; Zhen Feng; Baochen Li; Yimin Cai; Da Ouyang; Williamson Gustave; Chengfei Ying; Haibo Zhang (Journal of Hazardous Materials, 2023)

High adhesion hydrogel electrolytes enhanced by multifunctional group polymer enable high performance of flexible zinc-air batteries in wide temperature range - Zhihao Shang; Hang Zhang; Mengfei Qu; Ruiting Wang; Li Wan; Da Lei; Zhengzheng Li (Chemical Engineering Journal, 2023)

Quadruple modification for constructing ultra-stable lithium-rich cathodes - Chaoliang Zheng; Jiameng Feng; Zhicheng Wei; Da Zhang; Jianling Li (Chemical Engineering Journal, 2023)

Slope stability under the influence of irrigation and frozen stagnant water effect in Heifangtai - Guang Li; Ming-gao Tang; Ming-li Zhang; Da-lei Peng; Huan-le Zhao; Jian Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

In vitro digestion and fermentation combined with microbiomics and metabolomics reveal the mechanism of superfine yak bone powder regulating lipid metabolism by altering human gut microbiota - Jin Zhang; Xiaoqiong Li; Ke Zhao; Huanhuan Li; Jingnan Liu; Se Da; Dajie Ciren; Honggang Tang (Food Chemistry, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

3D Pore-Throat Microstructure Complexity of Igneous Reservoir Rock and its Effects on the Porosity–Permeability Relation - Mutian Qin; Shuyun Xie; Hongjun Li; Da Lou; Tianfu Zhang; Emmanuel John M. Carranza; Zhiwei Kuang (Natural Resources Research, 2023)

Runx2 overexpression promotes bone repair of osteonecrosis of the femoral head (ONFH) - Hai-Jia Xu; Xiang-Zhong Liu; Lu Yang; Yu Ning; Liang-Liang Xu; Da-Ming Sun; Wen Liao; Yi Yang; Zhang-Hua Li (Molecular Biology Reports, 2023)
Background Runt-related transcription factor-2 (Runx2) has been considered an inducer to improve bone repair ability of mesenchymal stem cells (MSCs). Methods and results Twenty-four rabbits were used to establish Osteonecrosis of the femoral head (ONFH) and randomly devided into four groups: Adenovirus Runx2 (Ad-Runx2) group, Runx2-siRNA group, MSCs group and Model group. At 1 week after model establishment, the Ad-Runx2 group was treated with 5 × 107 MSCs transfected through Ad-Runx2, the Runx2-siRNA group was treated with 5 × 107 MSCs transfected through Runx2-siRNA, the MSCs group was injected with 5 × 107 untreated MSCs, and the Model group was treated with saline. The injection was administered at 1 week and 3 weeks after model establishment. The expression of bone morphogenetic protein 2 (BMP-2), Runx2 and Osterix from the femoral head was detected at 3 and 6 weeks after MSCs being injected, and Masson Trichrome Staining, Gross Morphology, X-ray and CT images observation were used to evaluate the repair effect of ONFH. The data revealed that the expression of BMP-2, Runx2 and Osterix in the Runx2-siRNA group was reduced at 3 weeks compared with the MSCs group, and then the expression further reduced at 6 weeks, but was still higher than the Model group besides Osterix; The expression of these three genes in the Ad-Runx2 group was higher than in the MSCs group. Masson Trichrome Staining, Gross Morphology and X-ray and CT images observation revealed that necrotic femoral head of the MSCs group was more regular and smooth than the Runx2-siRNA group, which has a collapsed and irregular femoral head. In the Ad-Runx2 group, necrotic femoral head was basically completely repaired and covered by rich cartilage and bone tissue. Conclusions Overexpression of Runx2 can improve osteoblastic phenotype maintenance of MSCs and promote necrotic bone repair of ONFH.

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Effects of dietary supplementation of bovine lactoferrin on growth performance, immune function and intestinal health in weaning piglets - Xuanxuan Ma; Ya Hao; Ruoyu Mao; Na Yang; Xueling Zheng; Bing Li; Zhenlong Wang; Qingjuan Zhang; Da Teng; Jianhua Wang (BioMetals, 2023)

Simultaneous profiling of dust aerosol mass concentration and optical properties with polarized high-spectral-resolution lidar - Da Xiao; Nanchao Wang; Sijie Chen; Lingyun Wu; Detlef Müller; Igor Veselovskii; Chengcai Li; Eduardo Landulfo; Venkataraman Sivakumar; Jing Li; Huizheng Che; Jing Fang; et al. (Science of The Total Environment, 2023)

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

One-step preparation of photoresponsive microcapsules based on the interfacial self-assembly of an azopyridine coordination polymer - Jian Wang; Botian Li; Xianxiao Song; Xueyan Liu; Da Xiao; Yichi Zhang; Jundang Liang; Jianhong Xu (Chemical Engineering Journal, 2023)

Chemical constituents and biological activities of Artemisia argyi H.Lév. & vaniot - Yun-hong Zhang; Zhu-tao Shao; Guang-ming Bi; Yi-wei Sun; Yu-meng Wang; Da-li Meng (Natural Product Research, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

JA-induced TaMPK6 enhanced the freeze tolerance of Arabidopsis thaliana through regulation of ICE-CBF-COR module and antioxidant enzyme system - Meng-Meng Yu; Rui Wang; Jing-Qiu Xia; Chang Li; Qing-Hua Xu; Jing Cang; Yu-Ying Wang; Da Zhang (Plant Science, 2023)

Intensification of the East Asian winter monsoon resulted in greater preservation of terrestrial organic carbon on the inner shelf of the East China Sea since the last 1400 years - Shuai Liu; Da-Wei Li; Rong Xiang; Meng Yu; Hailong Zhang; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Axially chiral TADF-active materials with π-extended acceptors for highly efficient circularly polarized electroluminescence - Ke-Ke Tan; Da-Wei Zhang; Wen-Long Zhao; Meng Li; Chuan-Feng Chen (Chemical Engineering Journal, 2023)

Functional Autapses Form in Striatal Parvalbumin Interneurons but not Medium Spiny Projection Neurons - Xuan Wang; Zhenfeng Shu; Quansheng He; Xiaowen Zhang; Luozheng Li; Xiaoxue Zhang; Liang Li; Yujie Xiao; Bo Peng; Feifan Guo; Da-Hui Wang; Yousheng Shu (Neuroscience Bulletin, 2023)

Insight into the mechanism of gasification fine slag enhanced flotation with selective dispersion flocculation - Da Shi; Jianbo Zhang; Huiquan Li; Shaopeng Li; Fayu He; Jiangshan Qu; Ruiqi Chang; Ganyu Zhu; Chennian Yang; Chenye Wang (Fuel, 2023)

Adsorption behaviour and mechanism of Avermectin-based pesticides in soil driven by H-bonds formed between the compounds and humus - Tong-fang Jing; Da-xia Zhang; Yao-zhong Zhang; Yan Jin; Xian-zheng Han; Wei Mu; Bei-xing Li; Feng Liu (Chemical Engineering Journal, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Improving the genome and proteome annotations of the marine model diatom Thalassiosira pseudonana using a proteogenomics strategy - Xiao-Huang Chen; Ming-Kun Yang; Yuan-Yuan Li; Zhang-Xian Xie; Shu-Feng Zhang; Mats Töpel; Shady A. Amin; Lin Lin; Feng Ge; Da-Zhi Wang (Marine Life Science & Technology, 2023)
Diatoms are unicellular eukaryotic phytoplankton that account for approximately 20% of global carbon fixation and 40% of marine primary productivity; thus, they are essential for global carbon biogeochemical cycling and climate. The availability of ten diatom genome sequences has facilitated evolutionary, biological and ecological research over the past decade; however, a complimentary map of the diatom proteome with direct measurements of proteins and peptides is still lacking. Here, we present a proteome map of the model marine diatom Thalassiosira pseudonana using high-resolution mass spectrometry combined with a proteogenomic strategy. In-depth proteomic profiling of three different growth phases and three nutrient-deficient samples identified 9526 proteins, accounting for ~ 81% of the predicted protein-coding genes. Proteogenomic analysis identified 1235 novel genes, 975 revised genes, 104 splice variants and 234 single amino acid variants. Furthermore, our quantitative proteomic analysis experimentally demonstrated that a considerable number of novel genes were differentially translated under different nutrient conditions. These findings substantially improve the genome annotation of T. pseudonana and provide insights into new biological functions of diatoms. This relatively comprehensive diatom proteome catalog will complement available diatom genome and transcriptome data to advance biological and ecological research of marine diatoms.

Molecular mechanism of di-n-butyl phthalate promotion of bladder cancer development - En-Hui Li; Bai-Hui Xu; Hai-Bin Wei; Yu-Chen Bai; Qi Zhang; Wei-Wen Yu; Zhi-Hui Xu; Xiao-Long Qi; Da-Hong Zhang; Heng Wang (Toxicology in Vitro, 2023)

Do microplastics affect sulfamethoxazole sorption in soil? Experiments on polymers, ionic strength and fulvic acid - Ben Yu; Ting Zhao; Williamson Gustave; Baochen Li; Yimin Cai; Da Ouyang; Ting Guo; Haibo Zhang (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Pollen-based quantitative paleoclimatic record spanning the Mid-Brunhes Event in the Nihewan Basin, north China - Shuoqiang Da; Zhen Zhang; Yuecong Li; Qinghai Xu; Baoshuo Fan; Siyu Wang; Jin Dong; Yong Wang; Zhenqing Chi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Holdup of sub-granules towards enhanced production of anammox sludge in a dual circulation sludge bed reactor - Dongdong Xu; Wenda Chen; Chao Pan; Wenji Li; Leiyan Guo; Da Kang; Ping Zheng; Baolan Hu; Meng Zhang (Chemical Engineering Journal, 2023)

Constructing robust cathode/Li interfaces and intensifying ion transport kinetics for PEO-based solid-state lithium-sulfur batteries - Jin Li; Haitao Zhang; Yingyue Cui; Haoran Da; Hui Wu; Yingjun Cai; Suojiang Zhang (Chemical Engineering Journal, 2023)

Humic acid nature and compound structure together determine the capacity of soil to sorb Avermectin B1a and its derivatives - Tong-fang Jing; Da-xia Zhang; Yan Jin; Guo-dong Si; Bei-xing Li; Wei Mu; Feng Liu (Chemical Engineering Journal, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Correction to: Shoot organogenesis and plant regeneration from leaf and petiole explants of Corydalis saxicola Bunting - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2023)

Shoot organogenesis and plant regeneration from leaf and petiole explants of Corydalis saxicola Bunting - Jinhui Pang; Yuping Xiong; Yujie Zeng; Xiaohong Chen; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2023)
Corydalis saxicola Bunting, a medicinal herb known for alkaloids, grows mainly in Guizhou province and northwest Guangxi province of China. In this study, for the first time for this plant, an efficient adventitious shoot proliferation and regeneration system via shoot organogenesis from leaf and petiole explants was established. Cytokinins, including 6-benzyladenine (BA) and thidiazuron (TDZ), induced callus and then shoot organogenesis. Most adventitious shoots were induced from leaf explants on Murashige and Skoog (MS) medium (pH 6.5) supplemented with 2.0 µM BA and 0.5 µM α-naphthaleneacetic acid (NAA). This medium was also optimal for shoot proliferation. The rooting ½MS medium was supplemented with 1.0 µM indole-3-butyric acid (IBA) and 0.2 µM NAA; 95.7% of shoots induced roots within 30 d and 91% of plantlets survived on a peat:vermiculite (1:1, v:v) substrate after 90 d.

A cDNA-based reverse genetics system for feline calicivirus identifies the 3′ untranslated region as an essential element for viral replication - Jie Cheng; Aoxing Tang; Jing Chen; Da Zhang; Chunchun Meng; Chuanfeng Li; Hulai Wei; Guangqing Liu (Archives of Virology, 2023)

Evaluation on prevention and treatment of cuminaldehyde in culture of shrimp against white spot syndrome virus - Xu Zhang; Li-Hua Hu; Da-Wei Song; Yang Hu; Jiong Chen (Aquaculture, 2023)

Surface-enhanced Raman spectroscopy for environmental monitoring using gold clusters anchored on reduced graphene oxide - Xiangyu Zhang; Kai Zhao; Xianhui Wang; Hongbin Wang; Wenrong Yang; Jingquan Liu; Da Li (Science of The Total Environment, 2023)

Technological development pathway for carbon neutrality in China - Siyue Guo; Yu Liu; Weichen Zhao; Jiaquan Li; Guangwen Hu; Hui Kong; Yifan Gu; Bang Xu; Xiaodan Huang; Yan Zheng; Shihan Zhang; Da Zhang; et al. (Science Bulletin, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Identification and function of miRNA-mRNA interaction pairs during lateral root development of hemi-parasitic Santalum album L. seedlings - Yuan Li; Feng Jin; Xiuju Wu; Jaime A. Teixeira da Silva; Yuping Xiong; Xinhua Zhang; Guohua Ma (Journal of Plant Physiology, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Stacking pattern induced high ZTs in monolayer SnSSe and bilayer SnXY (X/Y = S, Se) materials with strong anharmonic phonon scattering - Shulin Bai; Mengxiu Wu; Jingyi Zhang; Dongming Luo; Da Wan; Xiaodong Li; Shuwei Tang (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Rhizosphere soil microbes benefit carbon and nitrogen sinks under long-term afforestation on the Tibetan Plateau - Ruixuan Liu; Yuan Yao; Qing Li; Zeyu Cai; Da Wei; Xiaodan Wang; Sheng Zhang (CATENA, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Stability analysis of Gongjiacun landslide in the three Gorges Reservoir area under the action of reservoir water level fluctuation and rainfall - Tian-shun Hou; Guang-li Xu; Da-qian Zhang; Hao-yu Liu (Natural Hazards, 2022)

CAF-derived midkine promotes EMT and cisplatin resistance by upregulating lncRNA ST7-AS1 in gastric cancer - Ke-Da Yang; Ying Wang; Fan Zhang; Qing-Ling Li; Bai-Hua Luo; De-Yun Feng; Zhi-Jun Zeng (Molecular and Cellular Biochemistry, 2022)

The complete chloroplast genome sequences of three lilies: genome structure, comparative genomic and phylogenetic analyses - Yuan Li; LiNa Zhang; TianXi Wang; ChaoChao Zhang; RuiJia Wang; Da Zhang; YuQi Xie; NingNing Zhou; WeiZhen Wang; HuiMin Zhang; Bin Hu; WenHan Li; et al. (Journal of Plant Research, 2022)

A novel hollow microsphere composite MnOx/PAA: effective catalyst for ozone decomposition at high humidity - Wei Liu; Jingwen Zhang; Zhao Dai; Ning Luo; Jing Qu; Peiyun Sun; Da Li; Weilong Liao; Junfu Wei; Huan Zhang (Environmental Science and Pollution Research, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

A single-cell survey unveils cellular heterogeneity and sensitive responses in mouse cortices induced by oral exposure to triphenyl phosphate - Di Ji; Yuejin Yu; Qicheng Zhu; Xianjie Li; Xiali Zhong; Zhuyi Zhang; Weijian Ke; Congying Niu; Can Wang; Jingwei Wu; Da Chen; Maoyong Song; et al. (Archives of Toxicology, 2022)

Exogenous Ca2+ Associated with Melatonin Alleviates Drought-Induced Damage in the Woody Tree Dalbergia odorifera - El-Hadji Malick Cisse; Li-Jia Zhang; Yu-Jin Pu; Ling-Feng Miao; Da-Dong Li; Juan Zhang; Fan Yang (Journal of Plant Growth Regulation, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Protective effect of nicorandil against myocardial ischemia/reperfusion injury mediated via IL33/ST2 signaling pathway - Yi Zheng; Xueyin Li; Fan Zhang; Bo Zhao; Wanting Du; Da Sun; Guangping Li (Molecular and Cellular Biochemistry, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Constraints on ore-forming fluid evolution and guidance for ore exploration in the Zhaxikang Sb–Pb–Zn–Ag deposit in southern Tibet: insights from silver isotope fractionation of galena - Da Wang; Ryan Mathur; Youye Zheng; Hongjie Wu; Yiwen Lv; Gangyang Zhang; Ren Huan; Miao Yu; Yujie Li (Mineralium Deposita, 2022)

Different Surface Appearances Caused by Unbalanced Mn2+ Accumulation in Gallstones Consisting of Cholesterol and CaCO3 Obtained from a Patient After Cholecystectomy - Da-Yong Lu; Jin Zhang; Qiao-Li Liu; Hong-Guang Wang; Meng Cui (Biological Trace Element Research, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Shoot organogenesis from leaf and stem explants of Heliotropium foertherianum Diane and Hilger - Xincheng Yu; Xiaohong Chen; Yuping Xiong; Yujie Zeng; Zhenpeng Wei; Jinhui Pang; Xinhua Zhang; Yuan Li; Kunlin Wu; Songjun Zeng; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

Bioinformatics Analysis of the MicroRNA-Metabolic Gene Regulatory Network in Neuropathic Pain and Prediction of Corresponding Potential Therapeutics - Huai-Gen Zhang; Li Liu; Zhi-Ping Song; Da-Ying Zhang (Journal of Molecular Neuroscience, 2022)

Estimation of permafrost thermal behavior using Fourier series model - Yan-yu Zhang; Shu-ying Zang; Lin Zhao; Da-long Ma; Yue Lin; Hao Li (Journal of Mountain Science, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

HMGB1-RAGE Pathway Contributes to the Abnormal Migration of Endogenous Subventricular Zone Neural Progenitors in an Experimental Model of Focal Microgyria - Yi-Wen Mei; Tian-Lan Huang; Xin Chen; Si-Xun Yu; Jie Li; Zhi Zhang; Yang He; Da-qing Guo; Hai-Feng Shu (Journal of Molecular Neuroscience, 2022)

Genetic improvement of grain quality traits in indica inbred rice cultivars developed in South China during 1956–2020 - Xin-Qiao Zhou; Da-Gang Chen; Jie Guo; Ping-Li Chen; Li-Jun Li; Ke Chen; You-Ding Chen; Chuan-Guang Liu; Ze-Min Zhang (Euphytica, 2022)

Experimental study of vertical and batter pile groups in saturated sand using a centrifuge shaking table - Zhang Jian; Li Yurun; Yan Zhixiao; Huang Da; Rong Xian; Liang Yan (Earthquake Engineering and Engineering Vibration, 2022)

Virtual screening of active compounds from jasminum lanceolarium and potential targets against primary dysmenorrhea based on network pharmacology - Caihong Liu; Li Liu; Jiaheng Li; Yunhong Zhang; Da-Li Meng (Natural Product Research, 2021)

On the Diurnal Cycle of Heavy Rainfall over the Sichuan Basin during 10–18 August 2020 - Rudi Xia; Yali Luo; Da-Lin Zhang; Mingxin Li; Xinghua Bao; Jisong Sun (Advances in Atmospheric Sciences, 2021)
A sustained heavy rainfall event occurred over the Sichuan basin in southwest China during 10–18 August 2020, showing pronounced diurnal rainfall variations with nighttime peak and afternoon minimum values, except on the first day. Results show that the westward extension of the anomalously strong western Pacific subtropical high was conducive to the maintenance of a southerly low-level jet (LLJ) in and to the southeast of the basin, which favored continuous water vapor transport and abnormally high precipitable water in the basin. The diurnal cycle of rainfall over the basin was closely related to the periodic oscillation of the LLJ in both wind speed and direction that was caused by the combination of inertial oscillation and terrain thermal forcing. The nocturnally enhanced rainfall was produced by moist convection mostly initiated during the evening hours over the southwest part of the basin where high convective available potential energy with moister near-surface moist air was present. The convective initiation took place as cold air from either previous precipitating clouds from the western Sichuan Plateau or a larger-scale northerly flow met a warm and humid current from the south. It was the slantwise lifting of the warm, moist airflow above the cold air, often facilitated by southwest vortices and quasi-geostrophic ascent, that released the convective instability and produced heavy rainfall.

Three new cycloart-7-ene triterpenoid glycosides from Cimicifuga dahurica and their anti-inflammatory effects - Qian-Qian Pang; Yu-Dan Mei; Yuan-Chu Zhang; Ling-Xian Liu; Dan-Feng Shi; Da-Bo Pan; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2021)

Synthesis of pyrazole-4-carboxamides as potential fungicide candidates - Cuntao Dong; Wei Gao; Xiaotian Li; Susu Sun; Jingqian Huo; Yanen Wang; Da Ren; Jinlin Zhang; Lai Chen (Molecular Diversity, 2021)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Psychological and occupational impact on healthcare workers and its associated factors during the COVID-19 outbreak in China - Xiaodan Zhang; Ye Jiang; Hu Yu; Yafen Jiang; Qiongfeng Guan; Weihe Zhao; Yingying Mao; Danfeng Huang; Wenke Hong; Da Li (International Archives of Occupational and Environmental Health, 2021)

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

Decreased calcium concentration interferes with life history defense strategies of Ceriodaphnia cornuta in response to fish kairomone - Jing Huang; Xiaoqing Xu; Da Li; Yunfei Sun; Lei Gu; Lu Zhang; Kai Lyu; Zhou Yang (Limnology and Oceanography, 2021)
Declining calcium in freshwater lakes has become a serious threat to aquatic organisms, which may affect the anti‐fish defense of cladocerans with high calcium demand. To evaluate the effects of low calcium on life history strategies of cladocerans for defending against fish predation, we exposed Ceriodaphnia cornuta to eight concentrations of calcium ranging from 0.5 to 50.0 mg L −1 in the absence and presence of fish kairomone, and observed the changes in body surface, recorded the key life‐history traits, and calculated the degree of its induced defense response. Results showed that, on average, low calcium (0.5, 1.0, 1.5 mg L −1 ) significantly reduced survival, maternal body size at maturation, and total offspring per female by 66.7%, 8.0%, and 48.8%, respectively, compared with those exposed to normal calcium level (10.0 mg L −1 ). At the normal calcium level, fish kairomone shortened the time to maturation, reduced maternal body size at maturation, and increased total offspring by 15.7%, 11.0%, and 29.6%, respectively, compared with those not exposed to fish kairomone. In the presence of fish kairomone, the reproduction of C. cornuta was affected by a narrower range of calcium concentrations. Calcium concentrations and fish kairomone showed a significant interaction on maternal body size at maturation, total offspring, and body size of neonates, i.e., low calcium impaired the life history defenses involved in maternal development, but enhanced the defense traits involved in reproductive performance, which indicated the diversified interference effects of decreased calcium on the life history defense strategies of C. cornuta against fish predators.

Neuroprotective triterpene saponins from the leaves of Panax notoginseng - Ji-Wu Huang; Yi-Qian Du; Chuang-Jun Li; Jing-Zhi Yang; Jie Ma; Ying-Da Zang; Nai-Hong Chen; Dong-Ming Zhang (Natural Product Research, 2021)

Correction to: TAK1 is involved in sodium L‑lactate‑stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Genetic characterization and phylogenetic analysis of duck-derived waterfowl parvovirus in Anhui province, eastern China - Yong Wang; Jianfei Sun; Da Zhang; Xu Guo; Wenhao Shen; Yongdong Li (Archives of Virology, 2021)

Investigation on Hydrodynamic Performance of Flapping Foil Interacting with Oncoming Von Kármán Wake of a D-Section Cylinder - Jian Li; Peng Wang; Xiaoyi An; Da Lyu; Ruixuan He; Baoshou Zhang (Journal of Marine Science and Engineering, 2021)
Flapping foils are studied to achieve an efficient propeller. The performance of the flapping foil is influenced by many factors such as oncoming vortices, heaving amplitude, and geometrical parameters. In this paper, investigations are performed on flapping foils to assess its performance in the wake of a D-section cylinder located half a diameter in front of the foil. The effects of heaving amplitude and foil thickness are examined. The results indicate that oncoming vortices facilitate the flapping motion. Although the thrust increases with the increasing heaving amplitude, the propelling efficiency decreases with it. Moreover, increasing thickness results in higher efficiency. The highest propelling efficiency is achieved when the heaving amplitude equals ten percent of the chord length with a symmetric foil type of NACA0050 foil. When the heaving amplitude is small, the influence of the thickness tends to be more remarkable. The propelling efficiency exceeds 100% and the heaving amplitude is 10% of the chord length when the commonly used equation is adopted. This result demonstrates that the flapping motion extracts some energy from the oncoming vortices. Based on the numerical results, a new parameter, the energy transforming ratio (RET), is applied to explicate the energy transforming procedure. The RET represents that the flapping foil is driven by the engine or both the engines and the oncoming vortices with the range of RET being (0, Infini) and (−1, 0), respectively. With what has been discussed in this paper, the oncoming wake of the D-section cylinder benefits the flapping motion which indicates that the macro underwater vehicle performs better following a bluff body.

Quantitative human risk analysis of 2015 Shenzhen dump failure considering influence of urbanization - Shuai Zhang; Ying Liu; Bate Bate; Da-lei Peng; Can Li; Liang-tong Zhan (Journal of Mountain Science, 2021)

TAK1 is involved in sodium L-lactate-stimulated p38 signaling and promotes apoptosis - Qingen Da; Zilong Yan; Zhangfu Li; Zhen Han; Mingming Ren; Lei Huang; Xiaowei Zhang; Jikui Liu; Tao Wang (Molecular and Cellular Biochemistry, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Fucoxanthin Mitigates Subarachnoid Hemorrhage-Induced Oxidative Damage via Sirtuin 1-Dependent Pathway - Xiang-Sheng Zhang; Yue Lu; Tao Tao; Han Wang; Guang-Jie Liu; Xun-Zhi Liu; Cang Liu; Da-Yong Xia; Chun-Hua Hang; Wei Li (Molecular Neurobiology, 2020)

Endoplasmic Reticulum Stress Regulates Cardiomyocyte Apoptosis in Myocardial Fibrosis Development via PERK-Mediated Autophagy - Changjiang Zhang; Yuanhong Li; Jingbo Zhao; Ke Su; Ke He; Yurong Da; Hao Xia (Cardiovascular Toxicology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Identification and full-genome sequencing of canine kobuvirus in canine fecal samples collected from Anhui Province, eastern China - Yong Wang; Yongqiu Cui; Yeqiu Li; Xiaopeng Wang; Kankan Yang; Da Zhang; Liang Zhao; Caixia Bai; Shudong Jiang; Yongdong Li (Archives of Virology, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Scientific and technological power and international cooperation in the field of natural hazards: a bibliometric analysis - Jing-Li Fan; Shuo Shen; Jian-Da Wang; Shi-Jie Wei; Xian Zhang; Ping Zhong; Hang Wang (Natural Hazards, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Sideswiping Tropical Cyclones and Their Associated Precipitation over China - Tian Feng; Fumin Ren; Da-Lin Zhang; Guoping Li; Wenyu Qiu; Hui Yang (Advances in Atmospheric Sciences, 2020)

Karstification of Ordovician carbonate reservoirs in Huanghua depression and its control factors - Jinning Zhang; Jiansheng Zhou; Lixin Fu; Hongjun Li; Da Lou (Carbonates and Evaporites, 2020)
With extensive ancient karsts and abundant oil and gas resources, the Ordovician carbonate reservoirs in the Huanghua depression have broad prospects of exploration and development. The types, characteristics, distribution and controlling factors of karsts were investigated by means of the analysis of cores, thin slices, logging, seismic, and geochemical data in this study. The study reveals that the Ordovician carbonate reservoirs in the Huanghua depression falls into three main categories, pore type, pore-vug-fracture type and fracture type, of which, pore-vug-fracture reservoirs account for 62%. The epigenetic uniform karst mainly developed in the Late Ordovician to Early Carboniferous, while the differential karst developed in the Mesozoic. The uniform karstification mainly include chemical dissolution of the original carbonate rock, while the differential karstification not only include chemical dissolution but also hydraulic erosion and biochemical dissolution by organic acid. The burial karstification mainly involved the dissolution of the Ordovician reservoir by large amount of acidic fluids generated by the overlying Upper Paleozoic coal measure source rock while generating hydrocarbon. The dissolution caused by upwelling magmatic-tectonic hydrothermal fluids along faults also contributed to the formation of burial karst reservoirs. The sedimentation-diagenesis and paleogeomorphology-tectonic movement have certain control effects on the karstification of the Ordovician reservoirs in the Huanghua depression, determining the reservoir quality.

Lower sensitivity in responses to root competition and soil resource availability in a new wheat cultivar than in an old wheat landrace - Li Zhu; Nianxun Xi; Da-Yong Zhang (Plant and Soil, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Development of a rapid and sensitive europium (III) chelate microparticle-based lateral flow test strip for the detection and epidemiological surveillance of porcine epidemic diarrhea virus - Jianbo Liu; Hongyan Shi; Guangyi Cong; Jianfei Chen; Xin Zhang; Da Shi; Liyan Cao; Xiaobo Wang; Jialin Zhang; Zhaoyang Ji; Zhaoyang Jing; Li Feng (Archives of Virology, 2020)

Development of an indirect ELISA for detecting porcine deltacoronavirus IgA antibodies - Manman Lu; Qiuge Liu; Xiaobo Wang; Jialin Zhang; Xin Zhang; Da Shi; Jianbo Liu; Hongyan Shi; Jianfei Chen; Li Feng (Archives of Virology, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

An efficient micropropagation protocol for Metasequoia glyptostroboides Hu et Cheng from shoot segments of 2-year-old trees - Yuping Xiong; Shuangyan Chen; Beiyi Guo; Meiyun Niu; Xinhua Zhang; Yuan Li; Kunlin Wu; Feng Zheng; Jaime A. Teixeira da Silva; Songjun Zeng; Guohua Ma (Trees, 2020)

Correction to: NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Relative roles of formation and preservation on gold endowment along the Sanshandao gold belt in the Jiaodong gold province, China: importance for province- to district-scale gold exploration - Liang Zhang; David I. Groves; Li-Qiang Yang; Gong-Wen Wang; Xiang-Dong Liu; Da-Peng Li; Ying-Xin Song; Wei Shan; Si-Chen Sun; Zhao-Kun Wang (Mineralium Deposita, 2020)

NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Tissue-Specific Monoallelic Expression of Bovine AXL is Associated with DNA Methylation of Promoter DMR - Da Xu; Guannan Wang; Junliang Li; Cui Zhang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2019)

Glacier change in the Tanggula Mountains, Tibetan Plateau, in 1969–2015 - Hong-yu Duan; Xiao-jun Yao; Shi-yin Liu; Yong-peng Gao; Miao-miao Qi; Juan Liu; Da-hong Zhang; Xiao-feng Li (Journal of Mountain Science, 2019)

Endothelial retinoblastoma protein reduces abdominal aortic aneurysm development via promoting DHFR/NO pathway-mediated vasoprotection - Yu Cao; Da Xiong; Ruize Kong; Guolin Dai; Minghua Zhong; Li Li; Jinping Zhang; Lihong Jiang; Hongrong Li (Molecular and Cellular Biochemistry, 2019)

Isolation and characterization of a novel strain (YH01) of Micropterus salmoides rhabdovirus and expression of its glycoprotein by the baculovirus expression system - Sun-jian Lyu; Xue-mei Yuan; Hai-qi Zhang; Wei-da Shi; Xiao-ying Hang; Li Liu; Ying-lei Wu (Journal of Zhejiang University-SCIENCE B, 2019)

Coring of Antarctic Subglacial Sediments - Da Gong; Xiaopeng Fan; Yazhou Li; Bing Li; Nan Zhang; Raphael Gromig; Emma C. Smith; Wolf Dummann; Sophie Berger; Olaf Eisen; Jan Tell; Boris K. Biskaborn; et al. (Journal of Marine Science and Engineering, 2019)
Coring sediments in subglacial aquatic environments offers unique opportunities for research on paleo-environments and paleo-climates because it can provide data from periods even earlier than ice cores, as well as the overlying ice histories, interactions between ice and the water system, life forms in extreme habitats, sedimentology, and stratigraphy. However, retrieving sediment cores from a subglacial environment faces more difficulties than sediment coring in oceans and lakes, resulting in low yields from the most current subglacial sediment coring methods. The coring tools should pass through a hot water-drilled access borehole, then the water column, to reach the sediment layers. The access boreholes are size-limited by the hot water drilling tools and techniques. These holes are drilled through ice up to 3000–4000 m thick, with diameters ranging from 10–60 cm, and with a refreezing closure rate of up to 6 mm/h after being drilled. Several purpose-built streamline corers have been developed to pass through access boreholes and collect the sediment core. The main coring objectives are as follows: (i) To obtain undisturbed water–sediment cores, either singly or as multi-cores and (ii) to obtain long cores with minimal stratigraphic deformation. Subglacial sediment coring methods use similar tools to those used in lake and ocean coring. These methods include the following: Gravity coring, push coring, piston coring, hammer or percussion coring, vibrocoring, and composite methods. Several core length records have been attained by different coring methods, including a 290 cm percussion core from the sub-ice-shelf seafloor, a 400 cm piston core from the sub-ice-stream, and a 170 cm gravity core from a subglacial lake. There are also several undisturbed water–sediment cores that have been obtained by gravity corers or hammer corers. Most current coring tools are deployed by winch and cable facilities on the ice surface. There are three main limitations for obtaining long sediment cores which determines coring tool development, as follows: Hot-water borehole radial size restriction, the sedimentary structure, and the coring techniques. In this paper, we provide a general view on current developments in coring tools, including the working principles, corer characteristics, operational methods, coring site locations, field conditions, coring results, and possible technical improvements. Future prospects in corer design and development are also discussed.

A Two-Step GRIN Lens Coating for In Vivo Brain Imaging - Yupeng Yang; Lifeng Zhang; Zhenni Wang; Bo Liang; Giovanni Barbera; Casey Moffitt; Yun Li; Da-Ting Lin (Neuroscience Bulletin, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Fluids discrimination by ray-path elastic impedance inversion: A successful case from Sulige tight gas field - Da-Xing Wang; Hao-Fan Wang; Jin-Feng Ma; Yong-Gang Wang; Na Zhang; Lin Li (Applied Geophysics, 2019)

Design and Experiment of Clamper Used in Antarctic Subglacial Bedrock Drilling - Pavel Talalay; Xingchen Li; Da Gong; Xiaopeng Fan; Nan Zhang; Yang Yang; Yongwen Liu; Yunchen Liu; Ting Wang; Xiao Li (Journal of Marine Science and Engineering, 2019)
As a result of the severe natural environment with oxygen deficit in the Antarctic, using conventional manual work to screw and unscrew the drill pipe increases the labor intensity tremendously and causes an efficiency reduction. Therefore, it would be useful to design a clamper inside the drilling shelter, which could help to assemble and disassemble the ice core barrel with screw connection. This paper describes the design of and experiments with the clamper inside the movable drilling shelter. A related testing stand was also designed and built to experiment on relationships between the clamper motor current versus clamping torque and force. Through experimental data collation and calculation analysis, the following conclusions could be drawn: (1) according to the rotary ability of the Ice and Bedrock Electromechanical Drill (IBED) to calculate and determine the torque of clamper, the clamping torque required to provide by the clamper is 100 N·m; (2) finite element simulation and analysis of the non-standard transmission chain showed that the mechanical reliability of the subparts; (3) the experimental results showed the range of the clamping force and clamping torque of the clamper. The clamping force and clamping torque increased with the increase of clamper DC motor current, presenting proportional linear relationships. The clamper can meet the clamping requirements of IBED for screwing, unscrewing, and clamping, which will be greatly helpful when it is tested in the field.

Population pharmacokinetics of oxcarbazepine active metabolite in Chinese paediatric epilepsy patients and its application in individualised dosage regimens - Wei-wei Lin; Xi-wen Li; Zheng Jiao; Jin Zhang; Xin Rao; Da-yong Zeng; Xin-hua Lin; Chang-lian Wang (European Journal of Clinical Pharmacology, 2019)

Influences of zinc oxide nanoparticles on Allium cepa root cells and the primary cause of phytotoxicity - Zhiqiang Sun; Tiantian Xiong; Ting Zhang; Nanfang Wang; Da Chen; Shaoshan Li (Ecotoxicology, 2019)

Time Effects on Resting EEG in Children With/Without AD/HD - Da-Wei Zhang; Stuart J. Johnstone; Hui Li; Robert J. Barry; Adam R. Clarke; Qihua Zhao; Yan Song; Lu Liu; Qiujin Qian; Yufeng Wang; Li Sun (Brain Topography, 2019)

LINC24065 is a monoallelically expressed long intergenic noncoding RNA located in the cattle DLK1–DIO3 cluster - Cui Zhang; Da Xu; Weina Chen; Junliang Li; Qinghua Gao; Shijie Li (Journal of Genetics, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Development of polymorphic microsatellite loci for Ceratosolen gravelyi (Hymenoptera: Agaonidae), the pollinating wasp of Ficus semicordata (Urticales: Moraceae) - Li-Yuan Yang; Ai-Ying Wang; Zhu-Zeng Huang; Rui-Wu Wang; Da-Yong Zhang (Applied Entomology and Zoology, 2019)

Whole-exome sequencing reveals SALL4 variants in premature ovarian insufficiency: an update on genotype–phenotype correlations - Qiqi Wang; Da Li; Baozhu Cai; Qing Chen; Caihua Li; Yanhua Wu; Li Jin; Xiuxia Wang; Xiaojin Zhang; Feng Zhang (Human Genetics, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Trophic Interaction in a Portunus rituberculatus Polyculture Ecosystem Based on Carbon and Nitrogen Stable Isotope Analysis - Jie Feng; Xiangli Tian; Shuanglin Dong; Da Li; Ruipeng He; Kai Zhang; Dongxu Zhang; Qingqi Zhang (Journal of Ocean University of China, 2018)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Polymorphic Imprinting of SLC38A4 Gene in Bovine Placenta - Da Xu; Cui Zhang; Junliang Li; Guannan Wang; Weina Chen; Dongjie Li; Shijie Li (Biochemical Genetics, 2018)

Energy metabolic enzyme responses of Litopenaeus vannamei to thermal stress: a comparative study in freshwater and seawater conditions - Xu-Ying Jia; Da-Sen Zhong; Dan Zhang; Fang Wang; Wen-Li Zhou (Aquaculture International, 2018)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Whole sequence analysis indicates a recent southern origin of Mongolian Y-chromosome C2c1a1a1-M407 - Yun-Zhi Huang; Lan-Hai Wei; Shi Yan; Shao-Qing Wen; Chuan-Chao Wang; Ya-Jun Yang; Ling-Xiang Wang; Yan Lu; Chao Zhang; Shu-Hua Xu; Da-Li Yao; Li Jin; et al. (Molecular Genetics and Genomics, 2018)

Late Mesozoic Tectonic Evolution of Southwestern Fujian Province, South China: Constraints from Magnetic Fabric, Zircon U-Pb Geochronology and Structural Deformation - Sen Wang; Da Zhang; Ganguo Wu; Xingjian Li; Xiaoqiao Gao; Absai Vatuva; Yuan Yuan; Tengda Yu; Yu Bai; Ye Fang (Journal of Earth Science, 2018)

HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .

The carbon footprints of secondary industry in China: an input–output subsystem analysis - Jing-Li Fan; Jian-Da Wang; Ling-Si Kong; Xian Zhang (Natural Hazards, 2018)

Metatranscriptome analysis reveals environmental and diel regulation of a Heterosigma akashiwo (raphidophyceae) bloom - Nanjing Ji; Lingxiao Lin; Ling Li; Liying Yu; Yaqun Zhang; Hao Luo; Meizhen Li; Xinguo Shi; Da‐Zhi Wang; Senjie Lin (Environmental Microbiology, 2018)
Summary Despite numerous laboratory studies on physiologies of harmful algal bloom (HAB) species, physiologies of these algae during a natural bloom are understudied. Here, we investigated a bloom of the raphidophyte Heterosigma akashiwo in the East China Sea in 2014 using metabarcode (18S rDNA) and metatranscriptome sequencing. Based on 18S rDNA analyses, the phytoplankton community shifted from high diversity in the pre‐bloom stage to H. akashiwo predominance during the bloom. A sharp decrease in ambient dissolved inorganic phosphate and strong up‐regulation of phosphate and dissolved organic phosphorus (DOP) uptake genes, including the rarely documented (ppGpp)ase, in H. akashiwo from pre‐bloom to bloom was indicative of rapid phosphorus uptake and efficient utilization of DOP that might be a driver of the H. akashiwo bloom. Furthermore, observed up‐regulated expression of mixotrophy‐related genes suggests potential contribution of mixotrophy to the bloom. Accelerating photosynthetic carbon fixation was also implied by the up‐regulation of carbonic anhydrase genes during the bloom. Notably, we also observed a strong morning‐to‐afternoon shift in the expression of many genes. Our findings provide insights into metabolic processes likely important for H. akashiwo bloom formation, and suggest the need to consider timing of sampling in field studies on this alga.

Detection and complete genome characteristics of Posavirus 1 from pigs in China - Jianfei Chen; Manman Lu; Tianxin Ma; Liyan Cao; Xiangdong Zhu; Xin Zhang; Da Shi; Hongyan Shi; Jianbo Liu; Li Feng (Virus Genes, 2018)

Metaproteomics reveals major microbial players and their metabolic activities during the blooming period of a marine dinoflagellate Prorocentrum donghaiense - Dong‐Xu Li; Hao Zhang; Xiao‐Huang Chen; Zhang‐Xian Xie; Yong Zhang; Shu‐Feng Zhang; Lin Lin; Feng Chen; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Interactions between bacteria and phytoplankton during bloom events are essential for both partners, which impacts their physiology, alters ambient chemistry and shapes ecosystem diversity. Here, we investigated the community structure and metabolic activities of free‐living bacterioplankton in different blooming phases of a dinoflagellate Prorocentrum donghaiense using a metaproteomic approach. The Fibrobacteres ‐ Chlorobi ‐ Bacteroidetes group, Rhodobacteraceae , SAR11 and SAR86 clades contributed largely to the bacterial community in the middle‐blooming phase while the Pseudoalteromonadaceae exclusively dominated in the late‐blooming phase. Transporters and membrane proteins, especially TonB‐dependent receptors were highly abundant in both blooming phases. Proteins involved in carbon metabolism, energy metabolism and stress response were frequently detected in the middle‐blooming phase while proteins participating in proteolysis and central carbon metabolism were abundant in the late‐blooming phase. Beta‐glucosidase with putative algicidal capability was identified from the Pseudoalteromonadaceae only in the late‐blooming phase, suggesting an active role of this group in lysing P . donghaiense cells. Our results indicated that diverse substrate utilization strategies and different capabilities for environmental adaptation among bacteria shaped their distinct niches in different bloom phases, and certain bacterial species from the Pseudoalteromonadaceae might be crucial for the termination of a dinoflagellate bloom.

Synthesis and antiproliferative properties of novel naringenin derivatives - Su-You Liu; Jiang Zeng; Kun-Jian Peng; Li-Chao Zhang; Li-Jun Liu; Zhi-Yong Luo; Da-You Ma (Medicinal Chemistry Research, 2017)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

A statistical analysis of hourly heavy rainfall events over the Beijing metropolitan region during the warm seasons of 2007–2014 - Huiqi Li; Xiaopeng Cui; Da‐Lin Zhang (International Journal of Climatology, 2017)
A statistical analysis of the spatiotemporal characteristics of hourly heavy rainfall ( HHR ) events and rainstorm days, defined as greater than 20 mm h −1 and 50 mm day −1 , respectively, is performed using observations at 5‐min intervals from 155 automated weather stations ( AWSs ) over the Beijing metropolitan region ( BMR ) during the warm seasons of 2007–2014. Results show pronounced variability in the frequencies and rainfall amounts of both HHR events and rainstorm days across the BMR of less than 150 km width from the west to east. That is, higher‐ (lower) frequency HHR events with more (less) accumulated rainfall amounts take place in eastern Haidian and over the BMR 's northeast mountains (west and northwest mountains). Many extreme rainfall and even record‐breaking events, in terms of the frequency, duration, rainfall amount and intensity, are found to occur in the regions of high‐frequency HHR events and rainstorm days. The frequency of rainstorm days with HHR events accounts for more than 50% of that of total rainstorm days over the BMR 's plains and near the northeast mountains. Results also show that HHR events occur most frequently in late July, and typically peak during 1600–2000 LST . A comparison of the averaged surface meteorological variables and upper‐air sounding at 0800 LST between HHR and non‐ HHR days reveals that the occurrences of the HHR events coincide with the distribution of surface warmer and more humid air as well as organized convergence in the presence of an unstable environment with surface south‐ to southeasterly winds, low‐level south to southwesterly flows and a deep layer of higher moisture content. These results suggest likely the positive influences of urban environment and mountain‐plain circulations on the generation of the HHR events, given favourable larger‐scale conditions.

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Enhancing the effectiveness of flood road gauges with color coding - Fang Jing; Li-Zhuang Yang; Ya-Li Peng; Ying Wang; Xiaochu Zhang; Da-Ren Zhang (Natural Hazards, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Anti-hepatocarcinoma activity of TT-1, an analog of melittin, combined with interferon-α via promoting the interaction of NKG2D and MICA - Lan-lan Wan; Da-qi Zhang; Jin-nan Zhang; Li-qun Ren (Journal of Zhejiang University-SCIENCE B, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

The chimeric nature of the genomes of marine magnetotactic coccoid‐ovoid bacteria defines a novel group of P roteobacteria - Boyang Ji; Sheng‐Da Zhang; Wei‐Jia Zhang; Zoe Rouy; François Alberto; Claire‐Lise Santini; Sophie Mangenot; Séverine Gagnot; Nadège Philippe; Nathalie Pradel; Lichen Zhang; Sébastien Tempel; et al. (Environmental Microbiology, 2017)
Summary Magnetotactic bacteria (MTB) are a group of phylogenetically and physiologically diverse Gram‐negative bacteria that synthesize intracellular magnetic crystals named magnetosomes. MTB are affiliated with three classes of Proteobacteria phylum, Nitrospirae phylum, Omnitrophica phylum and probably with the candidate phylum Latescibacteria. The evolutionary origin and physiological diversity of MTB compared with other bacterial taxonomic groups remain to be illustrated. Here, we analysed the genome of the marine magneto‐ovoid strain MO‐1 and found that it is closely related to Magnetococcus marinus MC‐1. Detailed analyses of the ribosomal proteins and whole proteomes of 390 genomes reveal that, among the Proteobacteria analysed, only MO‐1 and MC‐1 have coding sequences (CDSs) with a similarly high proportion of origins from Alphaproteobacteria , Betaproteobacteria , Deltaproteobacteria and Gammaproteobacteria . Interestingly, a comparative metabolic network analysis with anoxic network enzymes from sequenced MTB and non‐MTB successfully allows the eventual prediction of an organism with a metabolic profile compatible for magnetosome production. Altogether, our genomic analysis reveals multiple origins of MO‐1 and M. marinus MC‐1 genomes and suggests a metabolism‐restriction model for explaining whether a bacterium could become an MTB upon acquisition of magnetosome encoding genes.

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

New isocoumarin and stilbenoid derivatives from the tubers of Sparganium stoloniferum (Buch.-Ham.) - Da-Wei Wu; Qiao-Li Liang; Xiao-Long Zhang; Zheng Jiang; Xiu-He Fan; Wei Yue; Qi-Nan Wu (Natural Product Research, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Ming Cao; Zhu-Qin Gu; Yuan Li; Hui Zhang; Xiao-Juan Dan; Shan-Shan Cen; Da-Wei Li; Piu Chan (Neuroscience Bulletin, 2016)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Arctigenin Suppress Th17 Cells and Ameliorates Experimental Autoimmune Encephalomyelitis Through AMPK and PPAR-γ/ROR-γt Signaling - Wen Li; Zhihui Zhang; Kai Zhang; Zhenyi Xue; Yan Li; Zimu Zhang; Lijuan Zhang; Chao Gu; Qi Zhang; Junwei Hao; Yurong Da; Zhi Yao; et al. (Molecular Neurobiology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Amygdalin inhibits HSC-T6 cell proliferation and fibrosis through the regulation of TGF-β/CTGF - Huanhuan Luo; Liang Li; Jianbang Tang; Fengxue Zhang; Fang Zhao; Da Sun; Fengling Zheng; Xinhua Wang (Molecular & Cellular Toxicology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Comparative genomic analysis of Lactobacillus plantarum ZJ316 reveals its genetic adaptation and potential probiotic profiles - Ping Li; Xuan Li; Qing Gu; Xiu-yu Lou; Xiao-mei Zhang; Da-feng Song; Chen Zhang (Journal of Zhejiang University-SCIENCE B, 2016)

Ordovician intrusive rocks from the eastern Central Asian Orogenic Belt in Northeast China: chronology and implications for bidirectional subduction of the early Palaeozoic Palaeo-Asian Ocean - Hongying Li; Zhiguang Zhou; Pengju Li; Da Zhang; Changfeng Liu; XiaoQi Zhao; Lizhen Chen; Congnan Gu; Tingting Lin; Mengmeng Hu (International Geology Review, 2016)

Effects of Column Diameter on Setting Behavior of Dredged Slurry in Sedimentation Experiments - Yu-Feng Gao; Ying Zhang; Yuan Zhou; Da-yong Li (Marine Georesources & Geotechnology, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

The marine redox change and nitrogen cycle in the Early Cryogenian interglacial time: Evidence from nitrogen isotopes and Mo contents of the basal Datangpo Formation, northeastern Guizhou, South China - Wei Wei; Dan Wang; Da Li; Hongfei Ling; Xi Chen; Guangyi Wei; Feifei Zhang; Xiangkun Zhu; Bin Yan (Journal of Earth Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Immunogenicity and antigenic relationships among spike proteins of porcine epidemic diarrhea virus subtypes G1 and G2 - Xiaobo Wang; Jianfei Chen; Da Shi; Hongyan Shi; Xin Zhang; Jing Yuan; Shibo Jiang; Li Feng (Archives of Virology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

Drought tolerance of nitric oxide associated 1 mutant of Arabidopsis is mostly due to its reduced transpiration as a result of smaller stature - Wei Xu; Shuangshuang Zhang; Da-Li Wang; Jian-Zhong Liu (Acta Physiologiae Plantarum, 2015)

Fluoride Affects Calcium Homeostasis by Regulating Parathyroid Hormone, PTH-Related Peptide, and Calcium-Sensing Receptor Expression - Ying Wang; Xiao-qin Duan; Zhi-tao Zhao; Xiu-yun Zhang; Huan Wang; Da-wei Liu; Guang-sheng Li; Ling Jing (Biological Trace Element Research, 2015)

Association of novelty-related behaviors and intravenous cocaine self-administration in Diversity Outbred mice - Price E. Dickson; Juliet Ndukum; Troy Wilcox; James Clark; Brittany Roy; Lifeng Zhang; Yun Li; Da-Ting Lin; Elissa J. Chesler (Psychopharmacology, 2015)

Life history trait differentiation and local adaptation in invasive populations of Ambrosia artemisiifolia in China - Xiao-Meng Li; Deng-Ying She; Da-Yong Zhang; Wan-Jin Liao (Oecologia, 2015)

Relationship between haze and acute cardiovascular, cerebrovascular, and respiratory diseases in Beijing - Jin-jun Zhang; Meng-meng Cui; Da Fan; De-shan Zhang; Hui-xin Lian; Zhao-yin Yin; Jin Li (Environmental Science and Pollution Research, 2015)

Altered BDNF is correlated to cognition impairment in schizophrenia patients with tardive dyskinesia - Jing Qin Wu; Da Chun Chen; Yun Long Tan; Shu Ping Tan; Li Hui; Men Han Lv; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

H2O2 Induces Myocardial Hypertrophy in H9c2 Cells: A Potential Role of Ube3a - Rui Song; Jie Zhang; Lijuan Zhang; Guanghua Wang; Da Wo; Jian Feng; Xucheng Li; Jue Li (Cardiovascular Toxicology, 2015)

N-3 polyunsaturated fatty acids intake and risk of colorectal cancer: meta-analysis of prospective studies - Guo-Chong Chen; Li-Qiang Qin; Da-Bing Lu; Tie-Mei Han; Yan Zheng; Guo-Zhang Xu; Xiao-Huai Wang (Cancer Causes & Control, 2015)

Management of differentiated thyroid carcinoma with bone metastasis: a case report and review of the Chinese literature - Wei-dong Zhang; Da-ren Liu; Cheng-cheng Feng; Chuan-biao Zhou; Chen-ni Zhan; Ri-sheng Que; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Fluoride Affects Calcium Homeostasis and Osteogenic Transcription Factor Expressions Through L-type Calcium Channels in Osteoblast Cell Line - Xiao-qin Duan; Zhi-tao Zhao; Xiu-yun Zhang; Ying Wang; Huan Wang; Da-wei Liu; Guang-sheng Li; Ling Jing (Biological Trace Element Research, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Construction of Novel Chloroplast Expression Vector and Development of an Efficient Transformation System for the Diatom Phaeodactylum tricornutum - Wei-Hong Xie; Cong-Cong Zhu; Nai-Sheng Zhang; Da-Wei Li; Wei-Dong Yang; Jie-Sheng Liu; Ramalingam Sathishkumar; Hong-Ye Li (Marine Biotechnology, 2014)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Anti-tumor activity of the X-linked inhibitor of apoptosis (XIAP) inhibitor embelin in gastric cancer cells - Da-Guang Wang; Ya-Bin Sun; Fei Ye; Wei Li; Punyaram Kharbuja; Ling Gao; David Y. Zhang; Jian Suo (Molecular and Cellular Biochemistry, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular characterization of a porcine kobuvirus variant strain in China - Da Shi; Sha Zhang; Jianfei Chen; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

Analysis for remedial alternatives of unregulated municipal solid waste landfills leachate-contaminated groundwater - Da An; Yonghai Jiang; Beidou Xi; Zhifei Ma; Yu Yang; Queping Yang; Mingxiao Li; Jinbao Zhang; Shunguo Bai; Lei Jiang (Frontiers of Earth Science, 2013)

Defence responses of pepper (Capsicum annuum L.) infected with incompatible and compatible strains of Phytophthora capsici - Jun-E Wang; Da-Wei Li; Ying-Li Zhang; Qian Zhao; Yu-Mei He; Zhen-Hui Gong (European Journal of Plant Pathology, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

Zircon U–Pb geochronology and geochemistry of rhyolitic tuff, granite porphyry and syenogranite in the Lengshuikeng ore district, SE China: Implications for a continental arc to intra-arc rift setting - CHANGMING WANG; DA ZHANG; GANGUO WU; YIGAN XU; EMMANUEL JOHN M CARRANZA; YAOYAO ZHANG; HUAIKUN LI; JIANZHEN GENG (Journal of Earth System Science, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Genetic variation of nucleocapsid genes of porcine epidemic diarrhea virus field strains in China - Jianfei Chen; Xiaozhen Liu; Hongwu Lang; Zhongtian Wang; Da Shi; Hongyan Shi; Xin Zhang; Li Feng (Archives of Virology, 2013)

Evaluation of probiotic properties of Lactobacillus plantarum strains isolated from Chinese sauerkraut - Zhihui Yu; Xue Zhang; Shengyu Li; Changying Li; Da Li; Zhennai Yang (World Journal of Microbiology and Biotechnology, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Manufacture of Cheddar cheese using probiotic Lactobacillus plantarum K25 and its cholesterol-lowering effects in a mice model - Li Zhang; Xue Zhang; Chunhong Liu; Changying Li; Shengyu Li; Tiezhu Li; Da Li; Yujuan Zhao; Zhennai Yang (World Journal of Microbiology and Biotechnology, 2013)

Increased Expression of TRPV1 in the Cortex and Hippocampus from Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Wei Guo; Da-Hai Zheng; Chun-Qing Zhang; Song Li; Shi-Yong Liu; Qing Yin; Hui Yang; Hai-Feng Shu (Journal of Molecular Neuroscience, 2013)

Physiological responses and accumulation of pollutants in woody species under in situ polluted condition in Southern China - Ling-Ling Zhang; Hang-Er Wang; Jiong Li; Yuan-Wen Kuang; Da-Zhi Wen (Journal of Plant Research, 2013)

The screening and preliminary construction of quality mutant population for cultivar “Nipponbare” in japonica rice (Oryza sativa) - Da Peng Zhang; Jian Guo Wu; Guan Li; Chun Hai Shi (Biologia, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Evaluation of the predatory mite Amblyseius hainanensis (Acari: Phytoseiidae) and artificial rainfall for the management of Brevipalpus obovatus (Acari: Tenuipalpidae) - Da-Rui Zheng; Guang-Hua Liu; Run-Jie Zhang; Andrew G. S. Cuthbertson; Bao-Li Qiu (Experimental and Applied Acarology, 2012)

X-ray structure study of ranaconitine hydrobromide - Jun-Hui Zhou; Yang Li; Lei Zhang; Da-Qi Wang (Natural Product Research, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Association of CTLA-4 gene polymorphisms with sporadic breast cancer risk and clinical features in Han women of Northeast China - Dalin Li; Qiujin Zhang; Fengyan Xu; Zhenkun Fu; Weiguang Yuan; Dianjun Li; Da Pang (Molecular and Cellular Biochemistry, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Lowered Nudix type 5 (NUDT5) expression leads to cell cycle retardation in HeLa cells - Li-Qun Zhang; Da-Peng Dai; Wei Gan; Yasumitsu Takagi; Hiroshi Hayakawa; Mutsuo Sekiguchi; Jian-Ping Cai (Molecular and Cellular Biochemistry, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

XPD Lys751Gln polymorphism and esophageal cancer susceptibility: a meta-analysis of case–control studies - Da-Peng Ding; Wen-Li Ma; Xiao-Feng He; Ying Zhang (Molecular Biology Reports, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Important photosynthetic contribution from the non-foliar green organs in cotton at the late growth stage - Yuan-Yuan Hu; Ya-Li Zhang; Hong-Hai Luo; Wei Li; Riichi Oguchi; Da-Yong Fan; Wah Soon Chow; Wang-Feng Zhang (Planta, 2012)

Genetic transformation of Populus tomentosa to improve salt tolerance - Ningxia Du; Xin Liu; Yun Li; Shouyi Chen; Jinsong Zhang; Da Ha; Wenguang Deng; Chunkui Sun; Yingzhi Zhang; Paula M. Pijut (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

The effect of sevoflurane on the expression of M1 acetylcholine receptor in the hippocampus and cognitive function of aged rats - Sheng Peng; Yan Zhang; Guo-Jun Li; Deng-Xin Zhang; Da-Peng Sun; Qiang Fang (Molecular and Cellular Biochemistry, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Seasonal variation in population characteristics and management implications for brown rats (Rattus norvegicus) within their native range in Harbin, China - Da-Wei Wang; Lin Cong; Ling-Fen Yue; Bao-Huan Huang; Jian-Xu Zhang; Yu Wang; Ning Li; Xiao-Hui Liu (Journal of Pest Science, 2011)

Retinol, vitamins A, C, and E and breast cancer risk: a meta-analysis and meta-regression - Hu Fulan; Jiang Changxing; Wang Yi Baina; Zhang Wencui; Lin Chunqing; Wang Fan; Li Dandan; Sun Dianjun; Wang Tong; Pang Da; Zhao Yashuang (Cancer Causes & Control, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Analysis of the fungi community in multiple- and single-grains Zaopei from a Luzhou-flavor liquor distillery in western China - Si Shi; Lei Zhang; Zheng-yun Wu; Wen-xue Zhang; Yu Deng; Fang-da Zhong; Jia-min Li (World Journal of Microbiology and Biotechnology, 2011)

Gly-345 plays an essential role in Pyrococcus furiosus chaperonin function - Li-da Yang; Zhong-Mei Chu; Yi Zhang; Sheng-Li Yang (Biotechnology Letters, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Blood cells of a sisorid catfish Glyptosternum maculatum (Siluriformes: Sisoridae), in Tibetan Plateau - Hui Juan Zhang; Cong Xin Xie; Da Peng Li; Hai Ping Liu; Xue Feng Yang (Fish Physiology and Biochemistry, 2011)

The effect of sevoflurane anesthesia on cognitive function and the expression of Insulin-like Growth Factor-1 in CA1 region of hippocampus in old rats - Sheng Peng; Yan Zhang; Da-Peng Sun; Deng-Xin Zhang; Qiang Fang; Guo-Jun Li (Molecular Biology Reports, 2011)

Jeotgalibacillus soli sp. nov., isolated from non-saline forest soil, and emended description of the genus Jeotgalibacillus - Yi-Guang Chen; De-Jiao Peng; Qi-Hui Chen; Yu-Qin Zhang; Shu-Kun Tang; Da-Chun Zhang; Qing-Zhong Peng; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Comparison of reproductive strategies in two externally ovipositing non-pollinating fig wasps - Zhen-Ji Wang; Feng-Ping Zhang; Yan-Qiong Peng; Li-Fen Bai; Da-Rong Yang (Symbiosis, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Growth hormone and two forms of insulin-like growth factors I in the giant grouper (Epinephelus lanceolatus): molecular cloning and characterization of tissue distribution - Haiyan Dong; Lingxian Zeng; Da Duan; Haifa Zhang; Yunxin Wang; Wensheng Li; Haoran Lin (Fish Physiology and Biochemistry, 2010)

Geographic substructure of Fusarium asiaticum isolates collected from barley in China - Zheng Zhang; Hao Zhang; Theo van der Lee; Wan-Quan Chen; Paul Arens; Jin Xu; Jing-Sheng Xu; Li-Jun Yang; Da-Zhao Yu; Cees Waalwijk; Jie Feng (European Journal of Plant Pathology, 2010)

Down-Regulation of Stat3 Decreases Invasion Activity and Induces Apoptosis of Human Glioma Cells - Fuxue Chen; Yaming Xu; Youqun Luo; Da Zheng; Yichao Song; Kangkang Yu; Hong Li; Li Zhang; Weiwei Zhong; Yonghua Ji (Journal of Molecular Neuroscience, 2010)

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

The effects of CYP2C9 and CYP2C19 genetic polymorphisms on the pharmacokinetics and pharmacodynamics of glipizide in Chinese subjects - Bo Tan; Yi-Fan Zhang; Xiao-Yan Chen; Xiao-Hua Zhao; Guo-Xin Li; Da-Fang Zhong (European Journal of Clinical Pharmacology, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Genetic mapping of quantitative trait loci associated with β-amylase and limit dextrinase activities and β-glucan and protein fraction contents in barley - Kang Wei; Da-wei Xue; You-zong Huang; Xiao-li Jin; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Concentrations of sulphur and heavy metals in needles and rooting soils of Masson pine (Pinus massoniana L.) trees growing along an urban–rural gradient in Guangzhou, China - Fang Fang Sun; Da Zhi Wen; Yuan Wen Kuang; Jiong Li; Ji Guang Zhang (Environmental Monitoring and Assessment, 2009)

Gadolinium promoted proliferation and enhanced survival in human cervical carcinoma cells - Ying Zhang; Li-Juan Fu; Jin-Xia Li; Xiao-Gai Yang; Xiao-Da Yang; Kui Wang (BioMetals, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

Implication of reactive oxygen species and mitochondrial dysfunction in the early stages of plant programmed cell death induced by ultraviolet-C overexposure - Caiji Gao; Da Xing; Lingling Li; Lingrui Zhang (Planta, 2008)

Identification of new sources of aluminum resistance in wheat - Li-Li Zhou; Gui-Hua Bai; Brett Carver; Da-Dong Zhang (Plant and Soil, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

Metabolic effects of telmisartan in spontaneously hypertensive rats - Yong-Qi Li; Hui Ji; Yi-Hua Zhang; Da-Yong Ding; Xiao-Lei Ye (Naunyn-Schmiedeberg's Archives of Pharmacology, 2006)

Inhibitory effect of medroxyprogesterone acetate on human liver cytochrome P450 enzymes - Jiang-Wei Zhang; Yong Liu; Wei Li; Da-Cheng Hao; Ling Yang (European Journal of Clinical Pharmacology, 2006)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)

Spatial-temporal variation of heavy metal elements content in covering soil of reclamation area in fushun coal mine - Jun-bao Yu; Jing-shuang Liu; Jin-da Wang; Zhong-gen Li; Xue-lin Zhang (Chinese Geographical Science, 2002)

Chemical element transfer of weathering granite regolith in the Three Gorges Dam region of Yangtze River - Zhang Li-ping; Zhu Da-kui; Yang Da-yuan (Journal of Geographical Sciences, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)